Power storage device, and method for manufacturing method thereof
Patent Information
- Application Number
- JP2024023944
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-29
- Filing Date
- 2024-02-20
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2042-06-29
AI Technical Summary
The existing secondary batteries face issues with uneven pressure distribution when stacked due to the thicker seal portion acting as a fulcrum, leading to potential tilting and increased pressure variance, and corrosion risks from aluminum alloy foil short-circuiting with the external terminal.
The battery design includes a film-like exterior body with a non-overlapping first sealing portion and a specific aluminum alloy foil composition to prevent tilting and corrosion, featuring a barrier layer with controlled Fe and Mg content for enhanced corrosion resistance and mechanical strength.
This design effectively suppresses pressure unevenness and reduces corrosion, ensuring stable stacking and improved performance of multiple batteries by using a non-overlapping sealing structure and a corrosion-resistant aluminum alloy foil.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electricity storage device and a method for manufacturing an electricity storage device. [Background technology]
[0002] Japanese Patent No. 4509242 (Patent Document 1) discloses a secondary battery in which an electrode body is sealed in a bag made of an exterior member (laminate film) (see Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4509242 Summary of the Invention [Problem to be solved by the invention]
[0004] In the secondary battery disclosed in the above Patent Document 1, a seal part of an exterior member is provided on a surface having a large area. The seal part is thicker than other areas because it is an area where the exterior member overlaps. When other secondary batteries are stacked on the surface on which the seal part is provided, the upper secondary battery may tilt with the seal part as a fulcrum. As a result, the distribution of pressure applied to the lower secondary battery becomes more uneven.
[0005] In addition, when fine cracks or pinholes occur in the heat-sealable resin layer located in the innermost layer at the folded portion of the exterior member of the electric storage device, and when the external terminal and the aluminum alloy foil of the exterior member of the electric storage device are close to or in contact with each other to cause a short circuit, current flows between the aluminum alloy foil of the exterior member of the electric storage device and the external terminal through the electrolytic solution and electrolyte in contact with the heat-sealable resin layer, and the aluminum alloy foil may be alloyed and corroded with the lithium ions in the electrolytic solution. In particular, when the aluminum alloy foil and the negative electrode terminal are shorted through the electrolytic solution, the aluminum alloy foil is likely to corrode. When the aluminum alloy foil corrodes, problems such as the aluminum alloy foil expanding occur, leading to deterioration of the performance of the electric storage device.
[0006] The present invention has been made to solve such problems, and its object is to provide an electricity storage device that is corrosion-resistant and can suppress unevenness in the distribution of pressure applied to adjacent electricity storage devices when multiple electricity storage devices are stacked, and a method for manufacturing the electricity storage device. [Means for solving the problem]
[0007] An electricity storage device according to an aspect of the present invention includes an electrode body and an exterior body. The exterior body seals the electrode body. The exterior body is composed of a film-like exterior member. The exterior body includes a first sealing portion, a first surface, and a second surface that are sealed by bonding surfaces that face each other when the exterior member is wrapped around the electrode body. The area of the first surface is larger than the area of the second surface. The first sealing portion does not overlap the first surface in a plan view. The exterior member is composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The barrier layer includes an aluminum alloy foil that satisfies a composition of Fe: 0.2% by mass to 2.0% by mass and Mg: 0.1% by mass to 5.0% by mass.
[0008] In this electricity storage device, the first sealing portion does not overlap with the first surface having a larger area in a plan view. That is, the first sealing portion is not present on the first surface having a larger area. Therefore, even if another electricity storage device is arranged on or next to the first surface, the other electricity storage device will not tilt. As a result, according to this electricity storage device, unevenness in the distribution of pressure applied to adjacent electricity storage devices when multiple electricity storage devices are stacked can be suppressed. In addition, since the aluminum alloy foil of the exterior member has the above-mentioned configuration, the aluminum alloy foil is less susceptible to corrosion.
[0009] In the electricity storage device, the first sealing portion may be bent so as to be in contact with the second surface.
[0010] In the above electricity storage device, the first sealing portion may cover substantially the entire second surface when folded so as to be in contact with the second surface.
[0011] In this electricity storage device, the first sealing portion covers substantially the entire second surface, so that a wide bonding width can be ensured in the first sealing portion.
[0012] The power storage device further includes an electrode terminal electrically connected to the electrode body, and the outer casing further includes a second sealing portion sealed while sandwiching the electrode terminal, a portion of the electrode terminal is located outside the outer casing, and a root portion of the portion may be located at a position approximately halfway through the thickness of the power storage device in the thickness direction of the power storage device.
[0013] In this electricity storage device, a portion of the electrode terminal that is outside the exterior body is located at a position that is approximately halfway through the thickness of the electricity storage device in the thickness direction of the electricity storage device. Therefore, with this electricity storage device, it is possible to reduce the difference between the longest distance and the shortest distance between each of the multiple electrodes included in the electrode body and the electrode terminal, compared to a case in which the portion is located at approximately the same position as the first surface in the thickness direction of the electricity storage device.
[0014] In the above electricity storage device, in the first sealing portion, a region where the bonding strength between the surfaces is strong and a region where the bonding strength between the surfaces is weak may be arranged along the boundary between the first surface and the second surface.
[0015] In the above power storage device, in the first sealing portion, a thin region and a thick region may be arranged along the boundary between the first surface and the second surface.
[0016] The above electricity storage device may further include an electrode terminal electrically connected to the electrode body, and the first sealing portion may be sealed with the electrode terminal sandwiched therebetween.
[0017] The above-mentioned power storage device may further include an electrode terminal electrically connected to the electrode body and a lid body to which the electrode terminal is attached, and the exterior body may further include a second sealing portion that is sealed while joined to the lid body.
[0018] In the above electricity storage device, the lid body may include a first surface facing the electrode body and a second surface opposite the first surface, and the second sealing portion may include a portion where the exterior body and the second surface are joined.
[0019] The above-mentioned energy storage device may further include a lid body, and the exterior body may further include a second sealing portion sealed while being joined to the lid body, and the lid body may include a metal portion which is a portion having a metal layer exposed on its surface or which is made of a metal material, and the metal portion and the electrode body may be welded to each other.
[0020] In the above-mentioned energy storage device, the device may further include an electrode terminal electrically connected to the electrode body, and the exterior body may further include a protrusion that protrudes outward, and a second sealing portion that seals the electrode terminal while sandwiching it between the protrusions.
[0021] In the electricity accumulation device, the direction along the boundary between the first surface and the second surface may be a direction perpendicular to the flow direction of the exterior member.
[0022] In this electricity storage device, when the first sealing portion is folded along the boundary between the first and second surfaces, the direction along the boundary between the first and second surfaces is a direction perpendicular to the flow direction of the exterior member. Therefore, according to this electricity storage device, even if a crease is formed in the direction perpendicular to the flow direction of the exterior member, the exterior member is unlikely to break, and therefore it is possible to reduce the possibility that the first sealing portion will break when the first sealing portion is folded.
[0023] According to another aspect of the present invention, there is provided an electric storage device comprising an electrode assembly, an electrode terminal electrically connected to the electrode assembly, and an exterior body sealing the electrode assembly. The exterior body is made of a film-like exterior member and includes long sides and short sides in a plan view. The electrode terminal is disposed along the long sides.
[0024] An electric storage device according to another aspect of the present invention includes an electrode body and an exterior body. The exterior body seals the electrode body. The exterior body is constituted by an exterior member in the form of a film. The exterior body includes a piece portion in which the peripheral edges of the faces that face each other when wrapped around the electrode body are joined. A space is formed within the piece portion in which the faces that face each other are not joined. In the piece portion, a region in which the faces that face each other are joined and a region in which the faces that face each other are not joined are arranged near the boundary between the faces. The exterior member is constituted by a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The barrier layer includes an aluminum alloy foil that satisfies a composition of Fe: 0.2% by mass to 2.0% by mass and Mg: 0.1% by mass to 5.0% by mass.
[0025] Gas may be generated inside the exterior body. In this electricity storage device, a space is formed inside the one part, and a region where the opposing surfaces are joined and a region where the opposing surfaces are not joined are arranged near the boundary between the surfaces. Therefore, according to this electricity storage device, by releasing the sealed state of the exterior body at the one part, gas inside the exterior body can be discharged through the one part. Then, by sealing the exterior body again, a degassed electricity storage device can be manufactured. In addition, since the aluminum alloy foil of the exterior member has the above-mentioned configuration, the aluminum alloy foil is less likely to corrode.
[0026] In the electricity storage device, the aluminum alloy foil may have a composition satisfying the following: Si: 0.5 mass % or less.
[0027] In the above-mentioned electricity storage device, the composition of the aluminum alloy foil satisfies Mg: 0.1 mass % or more and 1.5 mass % or less, and at least one surface of the aluminum alloy foil contains 5.0 atomic percent or more of Mg, and at least one surface of the aluminum alloy foil may have an oxide film having a thickness of 80 Å or more.
[0028] In the electricity storage device, the aluminum alloy foil may have a composition satisfying Mg: 0.1% by mass or more and 1.5% by mass or less, and the aluminum alloy foil may have a tensile strength of 110 MPa or more and 180 MPa or less, and a breaking elongation of 10% or more.
[0029] In the above-mentioned electricity storage device, the composition of the aluminum alloy foil satisfies Mg: more than 1.5 mass% and not more than 5.0 mass%, and at least one surface of the aluminum alloy foil contains 15.0 atomic percent or more of Mg, and at least one surface of the aluminum alloy foil may have an oxide film having a thickness of 120 Å or more.
[0030] In the electricity storage device, the aluminum alloy foil may have a composition satisfying Mg: more than 1.5 mass % and not more than 5.0 mass %, and the aluminum alloy foil may have a tensile strength of 180 MPa or more and a breaking elongation of 15% or more.
[0031] In the electricity storage device, the aluminum alloy foil may have a texture with an orientation density of 15 or less for each of the Copper orientation and the R orientation.
[0032] In the electricity storage device, the aluminum alloy foil may have an average crystal grain size of 25 μm or less.
[0033] In the above-mentioned electricity storage device, the aluminum alloy foil may contain Al and inevitable impurities as the remainder, and the ratio of the length L1 of the high-angle grain boundary per unit area to the length L2 of the low-angle grain boundary measured by electron backscattering diffraction may satisfy the relationship L1 / L2>3.0.
[0034] In the electricity storage device, the aluminum alloy foil may contain 0.1% by mass or less of Mn as unavoidable impurities.
[0035] A method for manufacturing an electricity storage device according to another aspect of the present invention is a method for manufacturing an electricity storage device from an unfinished product. The unfinished product includes an electrode body and an exterior body. The exterior body seals the electrode body. The exterior body is composed of a film-shaped exterior member. The exterior body includes a piece in which the peripheral edges of the faces that face each other when the exterior member is wrapped around the electrode body are joined. A space is formed within the piece in which the faces that face each other are not joined. In the piece, a region in which the faces that face each other are joined and a region in which the faces that face each other are not joined are arranged near the boundary between the faces. The exterior member is composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The barrier layer includes an aluminum alloy foil that satisfies a composition of Fe: 0.2% by mass to 2.0% by mass and Mg: 0.1% by mass to 5.0% by mass. The manufacturing method includes a step of releasing the sealed state of the outer casing at one portion to discharge gas to the outside of the outer casing, and a step of resealing the outer casing by joining the mutually facing surfaces of at least a portion of the one portion.
[0036] According to this method for producing an electricity storage device, the gas is discharged through one portion, and the exterior body is then sealed again, whereby a degassed electricity storage device can be produced. Effect of the Invention
[0037] According to the present invention, it is possible to provide an electricity storage device that is corrosion-resistant and can suppress unevenness in the distribution of pressure applied to lower electricity storage devices when multiple electricity storage devices are stacked, and a method for manufacturing the electricity storage device. [Brief description of the drawings]
[0038] [Figure 1] FIG. 1 is a perspective view illustrating a schematic diagram of an electricity accumulation device according to a first embodiment. [Diagram 2] FIG. 2 is a plan view illustrating a schematic diagram of the electricity storage device. [Figure 3A] FIG. 2 is a side view illustrating a schematic diagram of the electricity storage device. [Figure 3B] FIG. 3 is a cross-sectional view showing an example of a layer structure of an exterior member. [Figure 3C] FIG. 3 is a cross-sectional view showing an example of a layer structure of an exterior member. [Figure 3D] FIG. 3 is a cross-sectional view showing an example of a layer structure of an exterior member. [Figure 3E] FIG. 3 is a cross-sectional view showing an example of a layer structure of an exterior member. [Figure 3F(A)] 1 is a micrograph showing the surface of an aluminum alloy foil used in evaluating corrosion resistance, the micrograph showing a surface free of corrosion. [Figure 3F(B)] 1 is a micrograph showing the surface of an aluminum alloy foil used in evaluating corrosion resistance, the micrograph showing a corroded surface. [Figure 4] 13 is a side view showing a state in which a packaging member is wrapped around an electrode body during manufacture of the electricity storage device according to the first embodiment. FIG. [Diagram 5] 13 is a view showing a state in which a packaging member is wrapped around an electrode body, as viewed from below, during manufacture of the electricity storage device according to the first embodiment. FIG. [Figure 6] 6 is a diagram showing a schematic view of a part of a cross section taken along line VI-VI in FIG. 2. [Figure 7] 11A to 11C are views for explaining a method of forming a second sealing portion. [Figure 8] 5 is a flowchart showing a manufacturing procedure for the electricity accumulation device according to the first embodiment. [Figure 9] FIG. 11 is a plan view illustrating a schematic diagram of an electricity accumulation device according to a second embodiment. [Figure 10] FIG. 2 is a side view illustrating a schematic diagram of the electricity storage device. [Figure 11] FIG. 2 is a perspective view showing a typical cover body. [Figure 12] FIG. 13 is a diagram showing a first example in which a lid and an electrode terminal are integrally formed. [Figure 13] FIG. 13 is a diagram showing a second example in which the cover and the electrode terminal are integrally formed. [Figure 14] 10 is a flowchart showing a manufacturing procedure for the electricity accumulation device according to the second embodiment. [Figure 15] 10 is a flowchart showing another manufacturing procedure for the electricity accumulation device according to the second embodiment. [Figure 16] FIG. 11 is a side view showing a state in which a sheath member is wrapped around an electrode body in a third embodiment. [Figure 17] FIG. 11 is a diagram showing a state in which an exterior member is wrapped around an electrode body and a lid body is attached to the exterior member, as viewed from below, in a third embodiment. [Figure 18] 13 is a flowchart showing a manufacturing procedure for the electricity accumulation device according to the third embodiment. [Figure 19] FIG. 13 is a plan view illustrating a schematic diagram of an electricity accumulation device according to a fourth embodiment. [Figure 20] FIG. 13 is a side view illustrating a schematic diagram of an electricity accumulation device according to a fourth embodiment. [Figure 21] FIG. 11 is a side view showing a state in which an exterior member is wrapped around an electrode body in a modified example. [Figure 22] FIG. 13 is a perspective view illustrating a modified example of an electricity storage device. [Figure 23] 13 is a perspective view showing a modified example of a cover and an electrode terminal attached to the cover. FIG. [Figure 24] FIG. 24 is a perspective view that illustrates a schematic diagram of an electricity accumulation device to which the lid of FIG. 23 is attached. [Diagram 25] FIG. 13 is a front view showing a schematic diagram of a cover according to another modified example. [Figure 26] FIG. 13 is a front view showing a schematic diagram of a cover according to still another modified example. [Figure 27] FIG. 11 is a plan view illustrating a schematic diagram of an electricity storage device according to another modified example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] Hereinafter, the embodiment of the present invention will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are given the same reference numerals and their description will not be repeated. In this specification, the numerical range indicated by "to" means "not less than" or "not more than". For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.
[0040] [1. First Embodiment] <1-1. Configuration of the power storage device> FIG. 1 is a perspective view that typically shows an electricity storage device 10 according to the first embodiment. FIG. 2 is a plan view that typically shows the electricity storage device 10. FIG. 3A is a side view that typically shows the electricity storage device 10. FIGS. 3B to 3E are cross-sectional views that show a layer structure of an exterior member 101 of the electricity storage device 10. In each of FIGS. 2 and 3A, the direction of arrows UD indicates the thickness direction of the electricity storage device 10, and the direction of arrows LR indicates the width direction of the electricity storage device 10. Furthermore, the direction of arrows FB indicates the depth direction of the electricity storage device 10. The directions indicated by the arrows UDLRFB are common to the subsequent figures.
[0041] 1, 2 and 3, the electricity storage device 10 includes an electrode body 200, an exterior body 100, and a plurality (two) of electrode terminals 300. The electrode body 200 includes electrodes (positive and negative electrodes) and separators constituting an electricity storage member such as a lithium ion battery, a capacitor, or an all-solid-state battery. The shape of the electrode body 200 is a substantially rectangular parallelepiped. Note that the term "substantially rectangular parallelepiped" includes not only a perfect rectangular parallelepiped, but also a solid body that can be regarded as a rectangular parallelepiped by modifying the shape of a portion of the outer surface, for example.
[0042] The electrode terminal 300 is a metal terminal used for inputting and outputting electric power in the electrode body 200. One end of the electrode terminal 300 is electrically connected to an electrode (positive electrode or negative electrode) included in the electrode body 200, and the other end protrudes outward from an edge of the exterior body 100.
[0043] The metal material constituting the electrode terminal 300 is, for example, aluminum, nickel, copper, etc. For example, when the electrode body 200 is a lithium ion battery, the electrode terminal 300 connected to the positive electrode is usually made of aluminum or the like, and the electrode terminal 300 connected to the negative electrode is usually made of copper, nickel, etc.
[0044] The exterior body 100 is composed of a film-like exterior member 101 (FIG. 4, etc.) and seals the electrode body 200. In the electricity storage device 10, the exterior body 100 is formed by wrapping the exterior member 101 around the electrode body 200 and sealing the open portion.
[0045] For example, there is a method of forming a storage portion (recess) for storing the electrode body 200 in the exterior member 101 through cold forming. However, it is not necessarily easy to form a deep storage portion by such a method. If an attempt is made to form a deep storage portion (recess) (for example, a forming depth of 15 mm) through cold forming, there is a high possibility that pinholes or cracks will occur in the exterior member, leading to a decrease in battery performance. On the other hand, since the exterior member 101 is wrapped around the electrode body 200 to seal the electrode body 200, the electrode body 200 can be easily sealed regardless of the thickness of the electrode body 200. Note that in order to reduce the dead space between the electrode body 200 and the exterior member 101 so as to improve the volumetric energy density of the electricity storage device 10, it is preferable that the exterior member 101 is wrapped around the electrode body 200 so as to come into contact with the outer surface of the electrode body 200. Moreover, in an all-solid-state battery, it is necessary to apply a high pressure uniformly from the outer surface of the battery in order to exert battery performance, and therefore it is necessary to eliminate the space between the electrode body 200 and the exterior member 101. Therefore, it is preferable that the exterior member 101 is wrapped around the electrode body 200 so as to be in contact with the outer surface of the electrode body 200.
[0046] 3B to 3E, the exterior member 101 is composed of a laminate including at least a base layer 101A, a barrier layer 101C, and a heat-sealable resin layer 101D in this order. In the exterior member 101, the base layer 101A is the outermost layer, and the heat-sealable resin layer 101D is the innermost layer. When assembling an electricity storage device using the exterior member 101 and an electricity storage device element, the heat-sealable resin layers 101D of the exterior member 101 are placed opposite each other, and the electrode body 200 is housed in a space formed by heat-sealing the peripheral portions.
[0047] The barrier layer 101C includes an aluminum alloy foil. That is, the barrier layer 101C can be made of an aluminum alloy foil. The exterior member 101 of this embodiment using an aluminum alloy foil that satisfies the predetermined composition and characteristics described below has excellent conformability to the exterior member at corners and the like, effectively suppresses corrosion of the aluminum alloy foil, and further has excellent mechanical strength.
[0048] As shown in Figures 3B to 3E, the exterior member 101 may have an adhesive layer 101B between the base layer 101A and the barrier layer 101C, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figures 3D and 3E, an adhesive layer 101E may be provided between the barrier layer 101C and the thermally adhesive resin layer 101D, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figure 3E, a surface coating layer 101F or the like may be provided on the outer side of the base layer 101A (the side opposite to the thermally adhesive resin layer 101D side) if necessary.
[0049] The thickness of the laminate constituting the exterior member 101 is not particularly limited, but from the viewpoint of cost reduction, energy density improvement, etc., examples of the thickness include 190 μm or less, preferably about 180 μm or less, about 155 μm or less, and about 120 μm or less. Moreover, from the viewpoint of maintaining the function of the exterior member 101 to protect the electrode assembly 200, the thickness of the laminate constituting the exterior member 101 is preferably about 35 μm or more, about 45 μm or more, and about 60 μm or more. Preferred ranges for the laminate constituting the exterior member 101 include, for example, about 35 to 190 μm, about 35 to 180 μm, about 35 to 155 μm, about 35 to 120 μm, about 45 to 190 μm, about 45 to 180 μm, about 45 to 155 μm, about 45 to 120 μm, about 60 to 190 μm, about 60 to 180 μm, about 60 to 155 μm, and about 60 to 120 μm, with about 60 to 155 μm being particularly preferred.
[0050] In the exterior member 101, the ratio of the total thickness of the base material layer 101A, the adhesive layer 101B provided as needed, the barrier layer 101C, the adhesion layer 101E provided as needed, the heat-sealable resin layer 101D, and the surface coating layer 101F provided as needed to the thickness (total thickness) of the laminate constituting the exterior member 101 is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more. As a specific example, when the exterior member 101 includes the base material layer 101A, the adhesive layer 101B, the barrier layer 101C, the adhesion layer 101E, and the heat-sealable resin layer 101D, the ratio of the total thickness of these layers to the thickness (total thickness) of the laminate constituting the exterior member 101 is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more.
[0051] In the exterior member 101, the MD (Machine Direction) and TD (Transverse Direction) of the barrier layer 101C described later can usually be determined in the manufacturing process. When the barrier layer 101C is made of an aluminum alloy foil, linear lines called rolling marks are formed on the surface of the metal foil in the rolling direction (RD) of the metal foil. Since the rolling marks extend along the rolling direction, the rolling direction of the metal foil can be determined by observing the surface of the metal foil. In addition, in the manufacturing process of the laminate, the MD of the laminate usually coincides with the RD of the metal foil, so that the MD of the laminate can be identified by observing the surface of the metal foil of the laminate and identifying the rolling direction (RD) of the metal foil. In addition, since the TD of the laminate is perpendicular to the MD of the laminate, the TD of the laminate can also be identified.
[0052] In addition, when the MD of the exterior member 101 cannot be identified due to the rolling marks of the aluminum alloy foil, it can be identified by the following method. As a method for confirming the MD of the exterior member 101, there is a method of observing the cross section of the heat-sealable resin layer of the exterior member 101 with an electron microscope to confirm the sea-island structure. In this method, the direction parallel to the cross section in which the average diameter of the shape of the islands in the direction perpendicular to the thickness direction of the heat-sealable resin layer was maximum can be determined as the MD. Specifically, the cross section in the length direction of the heat-sealable resin layer and each cross section (total of 10 cross sections) in which the angle is changed by 10 degrees from the direction parallel to the cross section in the length direction to the direction perpendicular to the cross section in the length direction are observed by electron microscope photographs to confirm the sea-island structure. Next, the shape of each individual island is observed in each cross section. For each island shape, the straight line distance connecting the leftmost end in the direction perpendicular to the thickness direction of the heat-sealable resin layer and the rightmost end in the perpendicular direction is defined as the diameter y. In each cross section, the average of the diameters y of the top 20 island shapes in descending order of the diameter y is calculated. The direction parallel to the cross section in which the average diameter y of the island shape was the largest was determined as MD.
[0053] <1-1-1. Base material layer> The base material layer 101A is a layer provided for the purpose of, for example, allowing the exterior member 101 to function as a base material. The base material layer 101A is located on the outer layer side of the exterior member 101.
[0054] The material for forming the base layer 101A is not particularly limited as long as it has the function of a base material, that is, at least insulating properties. The base layer 101A can be formed using, for example, a resin, and the resin may contain an additive described later.
[0055] When the base layer 101A is made of a resin, the base layer 101A may be, for example, a resin film made of a resin, or may be formed by applying a resin. The resin film may be an unstretched film or a stretched film. Examples of stretched films include uniaxially stretched films and biaxially stretched films, and biaxially stretched films are preferred. Examples of stretching methods for forming biaxially stretched films include sequential biaxial stretching, inflation, and simultaneous biaxial stretching. Examples of methods for applying a resin include roll coating, gravure coating, and extrusion coating.
[0056] Examples of the resin forming the base layer 101A include polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, and phenol resin, as well as modified versions of these resins. The resin forming the base layer 101A may be a copolymer of these resins, or a modified version of the copolymer. Furthermore, it may be a mixture of these resins.
[0057] Of these, preferred examples of the resin forming the base layer 101A include polyester and polyamide.
[0058] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters. Examples of copolymerized polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit. Specific examples of polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit and is polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), and polyethylene (terephthalate / decane dicarboxylate). These polyesters may be used alone or in combination of two or more.
[0059] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) that contain structural units derived from terephthalic acid and / or isophthalic acid, and polyamides containing aromatic compounds such as polyamide MXD6 (polymetaxylylene adipamide); alicyclic polyamides such as polyamide PACM6 (polybis(4-aminocyclohexyl)methane adipamide); polyamides copolymerized with a lactam component or an isocyanate component such as 4,4'-diphenylmethane diisocyanate; polyesteramide copolymers and polyetheresteramide copolymers that are copolymers of copolymerized polyamides with polyesters or polyalkylene ether glycols; and polyamides such as copolymers of these copolymers. These polyamides may be used alone or in combination of two or more.
[0060] The base layer 101A preferably includes at least one of a polyester film, a polyamide film, and a polyolefin film, preferably includes at least one of a stretched polyester film, a stretched polyamide film, and a stretched polyolefin film, more preferably includes at least one of a stretched polyethylene terephthalate film, a stretched polybutylene terephthalate film, a stretched nylon film, and a stretched polypropylene film, and even more preferably includes at least one of a biaxially oriented polyethylene terephthalate film, a biaxially oriented polybutylene terephthalate film, a biaxially oriented nylon film, and a biaxially oriented polypropylene film.
[0061] The base layer 101A may be a single layer, or may be composed of two or more layers. When the base layer 101A is composed of two or more layers, the base layer 101A may be a laminate in which resin films are laminated with an adhesive or the like, or may be a laminate of resin films in which resins are co-extruded to form two or more layers. In addition, a laminate of resin films in which resins are co-extruded to form two or more layers may be used as the base layer 101A without being stretched, or may be uniaxially or biaxially stretched to form the base layer 101A.
[0062] In the base layer 101A, specific examples of the laminate of two or more resin films include a laminate of a polyester film and a nylon film, a laminate of two or more nylon films, and a laminate of two or more polyester films, and preferably a laminate of a stretched nylon film and a stretched polyester film, a laminate of two or more stretched nylon films, and a laminate of two or more stretched polyester films. For example, when the base layer 101A is a laminate of two resin films, a laminate of a polyester resin film and a polyester resin film, a laminate of a polyamide resin film and a polyamide resin film, or a laminate of a polyester resin film and a polyamide resin film are preferred, and a laminate of a polyethylene terephthalate film and a polyethylene terephthalate film, a laminate of a nylon film and a nylon film, or a laminate of a polyethylene terephthalate film and a nylon film are more preferred. In addition, when the base layer 101A is a laminate of two or more resin films, it is preferred that the polyester resin film is located in the outermost layer of the base layer 101A, because the polyester resin is less likely to discolor when, for example, an electrolytic solution adheres to the surface.
[0063] When the base layer 101A is a laminate of two or more resin films, the two or more resin films may be laminated via an adhesive. As a preferred adhesive, the same adhesive as exemplified in the adhesive layer 101B described later can be used. The method for laminating two or more resin films is not particularly limited, and a known method can be adopted, for example, a dry lamination method, a sandwich lamination method, an extrusion lamination method, a thermal lamination method, etc., and preferably, a dry lamination method. When laminating by the dry lamination method, it is preferable to use a polyurethane adhesive as the adhesive. In this case, the thickness of the adhesive is, for example, about 2 to 5 μm. Also, an anchor coat layer may be formed on the resin film and laminated. As the anchor coat layer, the same adhesive as exemplified in the adhesive layer 101B described later can be used. In this case, the thickness of the anchor coat layer is, for example, about 0.01 to 1.0 μm.
[0064] In addition, additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, antistatic agents, etc. may be present on at least one of the surface and the interior of the base material layer 101A. Only one type of additive may be used, or two or more types may be mixed and used.
[0065] From the viewpoint of improving the conformability of the exterior member 101 at the corners of the exterior member 101, it is preferable that a lubricant is present on the surface of the base layer 101A. The lubricant is not particularly limited, but is preferably an amide-based lubricant. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, N,N'-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more kinds.
[0066] When a lubricant is present on the surface of the base layer 101A, the amount of the lubricant is not particularly limited, but is preferably about 3 mg / m 2 More preferably, 4 to 15 mg / m 2 about 5 to 14 mg / m 2 The degree of
[0067] The lubricant present on the surface of base layer 101A may be a lubricant exuded from the resin constituting base layer 101A, or a lubricant applied to the surface of base layer 101A.
[0068] The thickness of the base layer 101A is not particularly limited as long as it functions as a base, but may be, for example, about 3 to 50 μm, and preferably about 10 to 35 μm. When the base layer 101A is a laminate of two or more resin films, the thickness of each of the resin films constituting each layer is preferably about 2 to 25 μm.
[0069] <1-1-2.Adhesive layer> In exterior member 101, adhesive layer 101B is a layer that is provided between base layer 101A and barrier layer 101C as necessary for the purpose of increasing the adhesion between them.
[0070] The adhesive layer 101B is formed of an adhesive capable of bonding the base material layer 101A and the barrier layer 101C. The adhesive used to form the adhesive layer 101B is not limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, and the like. In addition, it may be a two-component curing adhesive (two-component adhesive), a one-component curing adhesive (one-component adhesive), or a resin that does not involve a curing reaction. In addition, the adhesive layer 101B may be a single layer or a multilayer.
[0071] Specific examples of adhesive components contained in the adhesive include polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolymerized polyamides; polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth)acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferred. In addition, the adhesive strength of these adhesive component resins can be increased by using an appropriate curing agent in combination. The curing agent is selected from polyisocyanates, multifunctional epoxy resins, oxazoline group-containing polymers, polyamine resins, acid anhydrides, and the like, depending on the functional groups of the adhesive components.
[0072] Examples of polyurethane adhesives include polyurethane adhesives containing a base agent containing a polyol compound and a curing agent containing an isocyanate compound. Preferably, a two-liquid curing type polyurethane adhesive is used in which a polyol such as polyester polyol, polyether polyol, or acrylic polyol is used as a base agent and an aromatic or aliphatic polyisocyanate is used as a curing agent. In addition, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the hydroxyl group at the end of the repeating unit as the polyol compound. Since the adhesive layer 101B is formed from a polyurethane adhesive, the exterior member 101 is given excellent electrolyte resistance, and the base material layer 101A is prevented from peeling off even if the electrolyte adheres to the side surface.
[0073] In addition, the adhesive layer 101B may contain other components as long as they do not impair adhesion, and may contain a colorant, a thermoplastic elastomer, a tackifier, a filler, etc. When the adhesive layer 101B contains a colorant, the exterior member 101 can be colored. As the colorant, known colorants such as pigments and dyes can be used. In addition, only one type of colorant may be used, or two or more types may be mixed together.
[0074] The type of pigment is not particularly limited as long as it does not impair the adhesiveness of the adhesive layer 101B. Examples of organic pigments include azo-based, phthalocyanine-based, quinacridone-based, anthraquinone-based, dioxazine-based, indigothioindigo-based, perinone-perylene-based, isoindolenine-based, and benzimidazolone-based pigments, and examples of inorganic pigments include carbon black-based, titanium oxide-based, cadmium-based, lead-based, chromium oxide-based, and iron-based pigments, as well as fine powder of mica and fish scale foil.
[0075] Among colorants, carbon black is preferable in order to give the exterior member 101 a black appearance, for example.
[0076] The average particle size of the pigment is not particularly limited and may be, for example, about 0.05 to 5 μm, and preferably about 0.08 to 2 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0077] The content of the pigment in adhesive layer 101B is not particularly limited as long as it colors exterior member 101, and may be, for example, about 5 to 60% by mass, and preferably 10 to 40% by mass.
[0078] The thickness of the adhesive layer 101B is not particularly limited as long as it can bond the base material layer 101A and the barrier layer 101C, but the lower limit is, for example, about 1 μm or more, about 2 μm or more, the upper limit is about 10 μm or less, about 5 μm or less, and preferred ranges are about 1 to 10 μm, about 1 to 5 μm, about 2 to 10 μm, and about 2 to 5 μm.
[0079] <1-1-3. Colored layer> The colored layer is a layer (not shown) that is provided between the base material layer 101A and the barrier layer 101C as necessary. When the adhesive layer 101B is provided, a colored layer may be provided between the base material layer 101A and the adhesive layer 101B, and between the adhesive layer 101B and the barrier layer 101C. A colored layer may also be provided on the outside of the base material layer 101A. By providing a colored layer, the exterior member 101 can be colored.
[0080] The colored layer can be formed, for example, by applying an ink containing a colorant to the surface of the base layer 101A, the surface of the adhesive layer 101B, or the surface of the barrier layer 101C. Known colorants such as pigments and dyes can be used as the colorant. Only one type of colorant may be used, or two or more types may be mixed together.
[0081] Specific examples of the colorant contained in the colored layer include the same as those exemplified for the adhesive layer 101B.
[0082] <1-1-4. Barrier layer> In exterior member 101, barrier layer 101C is a layer that at least prevents the infiltration of moisture.
[0083] Barrier layer 101C of exterior member 101 contains aluminum alloy foil. The characteristics of the aluminum alloy foil will be described below.
[0084] ·Fe: 0.2 mass% or more and 2.0 mass% or less Fe crystallizes as an Al-Fe intermetallic compound during casting, and when the size of the compound is large, it becomes a site of recrystallization during annealing, so that it has the effect of refining the recrystallized grains. If the Fe content is below the lower limit, the distribution density of the coarse intermetallic compounds is low, the effect of refining the crystal grains is low, and the final crystal grain size distribution is also non-uniform. If the content exceeds the upper limit, the effect of refining the crystal grains is saturated or even decreased, and further, the size of the Al-Fe intermetallic compounds generated during casting becomes very large, and the elongation and rollability of the foil are reduced. For this reason, the Fe content is set to the above range. For the same reason, the Fe content is preferably set to a lower limit of 0.5 mass%, and more preferably set to a lower limit of 1.0 mass% and an upper limit of 1.8 mass% for the same reason.
[0085] ·Mg: 0.1 mass% or more and 5.0 mass% or less Mg dissolves in aluminum and can increase the strength of the soft foil by solid solution strengthening. In addition, since Mg easily dissolves in aluminum, even if it is contained together with Fe, there is little risk that the intermetallic compounds will become coarse and the conformability and rollability of the exterior member at corners and the like will decrease. If the Mg content is below the lower limit, the improvement in strength will be insufficient, and if the Mg content is above the upper limit, the aluminum alloy foil will become hard, leading to a decrease in rollability and formability. The particularly preferred range of the Mg content is 0.5% by mass or more and 5.0% by mass or less.
[0086] It was also confirmed that the addition of Mg improves the corrosion resistance of lithium-ion secondary batteries to the electrolyte. Although the details of the mechanism are not clear, the more Mg is added, the less likely the aluminum alloy foil will react with the lithium in the electrolyte, and the more likely it is that the aluminum alloy foil will pulverize and develop through holes. Although the conformability of the exterior material at corners and other areas will decrease slightly, it is desirable to set the lower limit of the Mg content at 0.5 mass% even when a clear improvement in corrosion resistance is expected.
[0087] Preferably, Si: 0.5% by mass or less A small amount of Si may be added to increase the strength of the foil. In this embodiment, the composition of the aluminum alloy foil has a Si content of 0.5 mass% or less. Therefore, the size of the Al-Fe-Si intermetallic compounds generated during casting is reduced, and the elongation of the foil and the conformability of the exterior member at the corners and the like are improved. In addition, even if the foil thickness is thin, breakage starting from the intermetallic compounds is unlikely to occur, and the rollability is also good. In addition, by not adding a large amount of Si, the amount of Mg-Si precipitates generated is reduced, and the rollability and the amount of Mg in solid solution are unlikely to decrease, and the strength is unlikely to decrease. For the same reason, it is desirable to keep the Si content to 0.2 mass% or less. The lower the Si content, the better the conformability of the exterior member at the corners and the like, the rollability, the degree of grain refinement, and the ductility.
[0088] Inevitable impurities In addition, the aluminum alloy foil may contain inevitable impurities such as Cu and Mn. The amount of each element of these inevitable impurities is preferably 0.1 mass% or less. In this embodiment, the upper limit of the content of the inevitable impurities is not limited to the above numerical value.
[0089] However, since Mn is difficult to dissolve in aluminum, unlike Mg, it cannot be expected to significantly increase the strength of soft foils through solid solution strengthening. Also, adding a large amount of Mn to an alloy with a high Fe content increases the risk of coarsening of intermetallic compounds and the formation of giant Al-Fe-Mn intermetallic compounds, which may lead to a decrease in rollability and conformability of exterior components at corners, etc. For this reason, it is preferable to keep the Mn content at 0.1 mass% or less.
[0090] The orientation density of the copper orientation and R orientation of the texture is 15 or less. The texture has a significant effect on the mechanical properties of the foil and the ability of the exterior material to conform to corners, etc. If the density of either the copper orientation or the R orientation exceeds 15, there is a concern that uniform deformation during molding will not occur and the ability of the exterior material to conform to corners, etc. will decrease. In order to obtain the ability of the exterior material to conform to corners, etc., it is desirable to keep the density of the copper orientation and the R orientation each at 15 or less. More preferably, each orientation density is 10 or less.
[0091] The Mg concentration on the surface is 5.0 atomic percent or more, and the oxide film thickness is 80 Å or more (Mg: 0.1% by mass to 1.5% by mass). Although the details of the mechanism are not clear, it has been confirmed that the Mg concentration and oxide film thickness on the foil surface contribute to corrosion resistance against the electrolyte of lithium-ion secondary batteries. A high Mg concentration on the foil surface and the formation of a thick oxide film improves corrosion resistance. For this reason, when Mg is 0.1 mass% or more and 1.5 mass% or less, it is desirable to set the Mg concentration on the aluminum foil surface to 5.0 atomic percent or more and the oxide film thickness to 80 Å or more. More preferably, the Mg concentration on the surface is 15.0 atomic percent or more and the oxide film thickness is 200 Å or more. Even more preferably, the Mg concentration on the surface is 20.0 atomic percent or more. Here, the Mg concentration on the surface is the Mg concentration in the surface area from the outermost surface to a depth of 8 nm, and the Mg concentration is the amount relative to the total of all elements, 100 atomic %.
[0092] The Mg concentration on the surface is 15.0 atomic percent or more and the oxide film thickness is 120 Å or more (Mg: more than 1.5 mass% and less than 5.0 mass%) As mentioned above, although the details of the mechanism are not clear, it has been confirmed that the Mg concentration and oxide film thickness on the foil surface contribute to corrosion resistance against the electrolyte of lithium-ion secondary batteries. A high Mg concentration on the foil surface and the formation of a thick oxide film improves corrosion resistance. For this reason, when Mg is more than 1.5 mass% and 5.0 mass% or less, it is desirable to set the Mg concentration on the aluminum foil surface to 15.0 atomic percent or more and the oxide film thickness to 120 Å or more. More preferably, the Mg concentration on the surface is 20.0 atomic percent or more and the oxide film thickness is 220 Å or more. Even more preferably, the Mg concentration on the surface is 25.0 atomic percent or more.
[0093] When the length of a high-angle grain boundary per unit area measured by electron backscattering diffraction is L1 and the length of a low-angle grain boundary is L2, L1 / L2>3.0 The ratio of high-angle grain boundaries (HAGB; high-angle grain boundaries) and low-angle grain boundaries (LAGB; low-angle grain boundaries) in the recrystallized grain structure after annealing affects the elongation of the foil and the ability of the exterior member to follow corners, etc. If the ratio of LAGB is high in the recrystallized grain structure after final annealing, localization of deformation is likely to occur, and elongation and the ability of the exterior member to follow corners, etc. are reduced. For this reason, by increasing the ratio of HAGB by setting L1 / L2>3.0, high elongation and good ability of the exterior member to follow corners, etc. can be expected. More preferably, L1 / L2>5.0.
[0094] Tensile strength: 110MPa to 180MPa (Mg: 0.1% to 1.5% by mass) When Mg is 0.1% by mass or more and 1.5% by mass or less, a tensile strength of 110 MPa or more is required to dramatically improve impact resistance and puncture strength compared to existing foils such as JIS A8079 and 8021. In particular, to improve the conformability of exterior components at corners, etc., the tensile strength is preferably 180 MPa or less. The tensile strength can be achieved by selecting the composition and optimizing the crystal grain size.
[0095] Tensile strength: 180MPa or more (Mg: more than 1.5% by mass and less than 5.0% by mass) When Mg is more than 1.5% by mass and not more than 5.0% by mass, a tensile strength of 180 MPa or more is preferable in order to dramatically improve impact resistance and puncture strength compared to existing foils such as JIS A8079 and 8021. For the same reason, a tensile strength of 200 MPa or more is desirable. However, since the conformability of exterior components at corners and the like decreases as the tensile strength increases, it is better to keep the tensile strength low when conformability is important. As mentioned above, tensile strength can be achieved by selecting the composition and optimizing the crystal grain size.
[0096] Breaking elongation: 10% or more (Mg: 0.1% by mass or more and 1.5% by mass or less) The effect of elongation on the conformability of the exterior material at corners, etc. varies greatly depending on the forming method, and the conformability of the exterior material at corners, etc. is not determined by elongation alone. In the stretching process often used for aluminum packaging materials, the higher the elongation of the aluminum alloy foil, the better the conformability of the exterior material at corners, etc., and when Mg is 0.1% by mass or more and 1.5% by mass or less, it is desirable for the aluminum alloy foil to have an elongation of 10% or more. The elongation characteristics can be achieved by selecting the composition and refining the crystal grain size.
[0097] Elongation: 15% or more (Mg: more than 1.5% by mass and less than 5.0% by mass) As mentioned above, the effect of elongation on the conformability of an exterior material at corners and the like varies greatly depending on the forming method, and the conformability of an exterior material at corners and the like is not determined solely by elongation, but in the stretching process often used for aluminum packaging materials, the higher the elongation of the aluminum alloy foil, the more advantageous the conformability is, and when Mg is more than 1.5 mass% and not more than 5.0 mass%, it is desirable for the aluminum alloy foil to have an elongation of 15% or more. As mentioned above, the elongation characteristics can be achieved by selecting the composition and refining the crystal grain size.
[0098] ·Average grain size: 25μm or less The fine grains of soft aluminum alloy foils can suppress surface roughness during deformation, and are expected to provide high elongation and the ability to conform to exterior components at sharp corners. The thinner the foil, the greater the effect of grain size. To achieve high elongation and the ability to conform to exterior components at sharp corners, it is desirable for the average grain size to be 25 μm or less. The average grain size can be achieved by selecting the composition and optimizing manufacturing conditions such as homogenization treatment and cold rolling ratio.
[0099] The method for preparing the aluminum alloy foil will be described below. An aluminum alloy ingot is cast by a conventional method such as semi-continuous casting. The aluminum alloy ingot has a composition containing Fe: 0.2% by mass to 2.0% by mass, Mg: 0.1% by mass to 5.0% by mass, the balance being Al and unavoidable impurities, and Mn: 0.1% by mass or less as desired. The obtained ingot is subjected to homogenization treatment at 480 to 550°C for 6 to 12 hours.
[0100] Homogenization: 450~550℃ The homogenization process aims to eliminate microsegregation within the ingot and adjust the distribution of intermetallic compounds, and is a very important process for obtaining the final target crystal grain structure. Generally, homogenization of aluminum materials is carried out at 400 to 600° C. for a long period of time, but in the present invention, it is necessary to take into consideration the refinement of crystal grains by adding Fe. In homogenization treatment, at a temperature below 450°C, Fe precipitation is insufficient, and there is concern that the grains will become coarse during final annealing. In addition, the rate of in-situ recrystallization increases, and there is concern that the rate of LAGB will increase, and there is concern that L1 / L2 will decrease. In addition, there is concern that the followability of the exterior member at corners and the like will decrease due to the increase in the orientation density of the copper orientation and the R orientation. In addition, at a temperature above 550°C, crystallized substances grow significantly, leading to coarsening of grains during final annealing and a decrease in the followability of the exterior member at corners and the like. The time for homogenization treatment must be at least 3 hours. If it is less than 3 hours, precipitation is insufficient, and the density of fine intermetallic compounds will decrease. Desirably, the temperature is 480 to 520°C and the time is 5 hours or more.
[0101] After the homogenization treatment, hot rolling is performed to obtain an aluminum alloy sheet of a desired thickness. Hot rolling can be performed by a conventional method, but the coiling temperature in hot rolling is preferably equal to or higher than the recrystallization temperature, specifically, equal to or higher than 300°C. If the temperature is lower than 300°C, fine Al-Fe intermetallic compounds of 0.3 μm or less are precipitated. In addition, after hot rolling, recrystallized grains and fiber grains are mixed, and there is a concern that the grain size after intermediate annealing and final annealing becomes non-uniform and the elongation property decreases, which is undesirable.
[0102] After the hot rolling, cold rolling, intermediate annealing, and final cold rolling are performed to a thickness of 5 to 100 μm, thereby obtaining the aluminum alloy foil of the present invention. There are two types of intermediate annealing: batch annealing, in which the coil is placed in a furnace and held there for a certain period of time, and continuous annealing line (CAL annealing), in which the material is rapidly heated and cooled. Either method is acceptable when applying intermediate annealing, but CAL annealing is preferable when refining grains and increasing strength. However, there is a concern that the texture develops after final annealing through final cold rolling after CAL annealing, increasing the density of copper orientation and R orientation, and reducing the ability of the exterior material to follow corners, etc. For this reason, batch annealing is preferable if priority is given to the ability of the exterior material to follow corners, etc.
[0103] For example, in batch annealing, conditions of 300 to 400°C for 3 hours or more can be adopted. In CAL annealing, conditions of heating rate: 10 to 250°C / sec, heating temperature: 400 to 550°C, no holding time or holding time: 5 seconds or less, and cooling rate: 20 to 200°C / sec can be adopted. However, in the present invention, the presence or absence of intermediate annealing, and the conditions when intermediate annealing is performed are not limited to specific ones.
[0104] Final cold rolling ratio: 84.0% to 97.0% The higher the final cold rolling reduction ratio from the intermediate annealing to the final thickness, the more strain is accumulated in the material, and the finer the recrystallized grains are after the final annealing. It also has the effect of suppressing in-situ recrystallization, and it is expected that the followability of the exterior parts at corners and the like will improve with the increase in L1 / L2. Specifically, it is desirable to set the final cold rolling reduction ratio to 84.0% or more. However, if the final cold rolling reduction ratio is too high, there is a concern that the followability of the exterior parts at corners and the like will decrease due to the increase in the orientation density of the copper orientation and the R orientation even after the final annealing. As a result, L1 / L2 will also decrease, so specifically, it is desirable to set the final cold rolling reduction ratio to 97.0% or less. Furthermore, if the final cold rolling reduction ratio is low, there is a concern that the followability of the exterior parts at corners and the like will decrease due to the coarsening of the crystal grains and the decrease in L1 / L2. For the same reason, the more desirable range of the final cold rolling reduction ratio is 90.0% or more and 93.0% or less.
[0105] After the foil rolling, final annealing is performed to produce a soft foil. The final annealing after the foil rolling is generally performed at 250°C to 400°C. However, in order to enhance the effect of corrosion resistance due to Mg, it is preferable to hold the foil at a high temperature of 300°C or higher for 5 hours or more, and the temperature is more preferably 350°C to 400°C. If the final annealing temperature is low, softening will be insufficient, and there is a concern that the L1 / L2 ratio will decrease and the orientation density of the copper orientation and R orientation will increase. There is also a concern that the concentration of magnesium on the foil surface and the growth of the oxide film will be insufficient, resulting in a decrease in corrosion resistance. If the temperature exceeds 400°C, there is a concern that magnesium will be excessively concentrated on the foil surface, causing discoloration of the foil, and that the properties of the oxide film will change and microcracks will occur, resulting in a decrease in corrosion resistance. If the final annealing time is less than 5 hours, the effect of the final annealing will be insufficient.
[0106] The obtained aluminum alloy foil has, at room temperature, a tensile strength of 110 MPa or more and 180 MPa or less and an elongation of 10% or more when the Mg content is 0.1% by mass or more and 1.5% by mass or less. When the Mg content is more than 1.5% by mass and 5.0% by mass or less, the tensile strength is 180 MPa or more and an elongation of 15% or more. The average crystal grain size is 25 μm or less. The average crystal grain size can be determined by a cutting method specified in JIS G0551.
[0107] The thickness of the aluminum alloy foil needs to function as a barrier layer that prevents moisture from penetrating into exterior member 101, and the lower limit is about 9 μm or more, and the upper limit is about 200 μm or less. From the viewpoint of reducing the thickness of the exterior member 101, the upper limit of the thickness of the aluminum alloy foil is, for example, preferably about 85 μm or less, more preferably about 50 μm or less, even more preferably about 45 μm or less, and particularly preferably about 40 μm or less, and the lower limit is preferably about 10 μm or more, even more preferably about 20 μm or more, and more preferably about 25 μm or more. Preferred ranges of the thickness include about 10 to 85 μm, about 10 to 50 μm, about 10 to 45 μm, about 10 to 40 μm, about 20 to 85 μm, about 20 to 50 μm, about 20 to 45 μm, about 20 to 40 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 45 μm, and about 25 to 40 μm.
[0108] In addition, in order to suppress dissolution and corrosion of the aluminum alloy foil, it is preferable that at least one side of the aluminum alloy foil is provided with a corrosion-resistant film. The aluminum alloy foil may be provided with a corrosion-resistant film on both sides. Here, the corrosion-resistant film refers to a thin film that is provided with corrosion resistance by performing, for example, hydrothermal transformation treatment such as boehmite treatment, chemical conversion treatment, anodizing treatment, plating treatment such as nickel or chromium, or corrosion prevention treatment by applying a coating agent on the surface of the aluminum alloy foil. As a treatment for forming a corrosion-resistant film, one type may be performed, or two or more types may be combined. In addition, not only one layer but also multiple layers can be formed. Furthermore, among these treatments, hydrothermal transformation treatment and anodizing treatment are treatments in which the metal foil surface is dissolved by a treatment agent to form a metal compound having excellent corrosion resistance. Note that these treatments may be included in the definition of chemical conversion treatment. In addition, when the aluminum alloy foil has a corrosion-resistant film, the corrosion-resistant film is also included in the aluminum alloy foil.
[0109] The corrosion-resistant coating prevents delamination between the aluminum alloy foil and the base material layer during molding of the exterior member 101, prevents dissolution and corrosion of the aluminum alloy foil surface and dissolution and corrosion of aluminum oxide present on the aluminum alloy foil surface due to hydrogen fluoride produced by the reaction of the electrolyte with moisture, and improves the adhesion (wettability) of the aluminum alloy foil surface, thereby preventing delamination between the base material layer and the aluminum alloy foil during heat sealing and between the base material layer and the aluminum alloy foil during molding.
[0110] Various corrosion-resistant films formed by chemical conversion treatments are known, and mainly include corrosion-resistant films containing at least one of phosphates, chromates, fluorides, triazine thiol compounds, and rare earth oxides. Examples of chemical conversion treatments using phosphates and chromates include chromate chromate treatment, phosphoric acid chromate treatment, phosphoric acid-chromate treatment, and chromate treatment. Examples of chromium compounds used in these treatments include chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate. Examples of phosphorus compounds used in these treatments include sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid. Examples of chromate treatments include etching chromate treatment, electrolytic chromate treatment, and coating-type chromate treatment, and coating-type chromate treatment is preferred. In this coating type chromate treatment, at least the inner layer side of the barrier layer (e.g., aluminum alloy foil) is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is coated with a treatment liquid mainly composed of a metal phosphate such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, or Zn (zinc) phosphate, or a mixture of these metal salts, or a treatment liquid mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid consisting of a mixture of these with a synthetic resin, or the like, by a known coating method such as a roll coating method, a gravure printing method, or a dipping method, and then dried. As the treatment liquid, various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents can be used, and water is preferred. Examples of the resin component used here include polymers such as phenolic resins and acrylic resins, and chromate treatment using an aminated phenol polymer having repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.The acrylic resin is preferably polyacrylic acid, acrylic acid methacrylic acid ester copolymer, acrylic acid maleic acid copolymer, acrylic acid styrene copolymer, or a derivative thereof such as sodium salt, ammonium salt, or amine salt. In particular, a derivative of polyacrylic acid such as an ammonium salt, sodium salt, or amine salt of polyacrylic acid is preferable. In this embodiment, polyacrylic acid means a polymer of acrylic acid. In addition, the acrylic resin is also preferably a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride, and is also preferably an ammonium salt, sodium salt, or amine salt of a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride. Only one type of acrylic resin may be used, or two or more types may be mixed and used.
[0111] [ka]
[0112] [ka]
[0113] [ka]
[0114] [ka]
[0115] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxy group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each independently represent a hydroxy group, an alkyl group, or a hydroxyalkyl group. 1 and R 2Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) to (4) include linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group represented by the following formulae may be the same or different. In the general formulae (1) to (4), X is preferably a hydrogen atom, a hydroxy group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the general formulae (1) to (4) is preferably about 500 to 1,000,000, for example, and more preferably about 1,000 to 20,000. The aminated phenol polymer can be prepared, for example, by polycondensing a phenol compound or a naphthol compound with formaldehyde to produce a polymer consisting of the repeating units represented by the above general formula (1) or (3), and then polycondensing the polymer with formaldehyde and an amine (R 1 R 2 NH) to the functional group (-CHNR 1 R 2 The aminated phenol polymers can be used alone or in combination of two or more.
[0116] Another example of the corrosion-resistant film is a thin film formed by a coating-type corrosion prevention treatment in which a coating agent containing at least one selected from the group consisting of rare earth element oxide sol, anionic polymer, and cationic polymer is applied. The coating agent may further contain phosphoric acid or a phosphate, and a crosslinking agent for crosslinking the polymer. The rare earth element oxide sol has rare earth element oxide fine particles (for example, particles with an average particle size of 100 nm or less) dispersed in a liquid dispersion medium. Examples of rare earth element oxides include cerium oxide, yttrium oxide, neodymium oxide, and lanthanum oxide, and cerium oxide is preferred from the viewpoint of further improving adhesion. The rare earth element oxide contained in the corrosion-resistant film can be used alone or in combination of two or more. Examples of the liquid dispersion medium for the rare earth element oxide sol include various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents, and water is preferred. As the cationic polymer, for example, polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or its derivative, aminated phenol, etc. are preferable. In addition, as the anionic polymer, poly(meth)acrylic acid or its salt, or a copolymer mainly composed of (meth)acrylic acid or its salt, is preferable. In addition, it is preferable that the crosslinking agent is at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. In addition, it is preferable that the phosphoric acid or the phosphoric acid salt is a condensed phosphoric acid or a condensed phosphate salt.
[0117] One example of a corrosion-resistant coating is one formed by applying a solution of fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate dispersed in phosphoric acid to the surface of a barrier layer and baking the coating at 150°C or higher.
[0118] If necessary, the corrosion-resistant coating may have a laminated structure in which at least one of a cationic polymer and an anionic polymer is further laminated. Examples of the cationic polymer and anionic polymer include those mentioned above.
[0119] The composition of the corrosion-resistant film can be analyzed by, for example, time-of-flight secondary ion mass spectrometry.
[0120] The amount of the corrosion-resistant film formed on the surface of the aluminum alloy foil in the chemical conversion treatment is not particularly limited. For example, in the case of a coating-type chromate treatment, the amount of the corrosion-resistant film formed on the surface of the aluminum alloy foil is preferably 1 mm. 2 It is desirable that the chromate compound is contained in an amount, calculated as chromium, of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, the phosphorus compound is contained in an amount, calculated as phosphorus, of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, and the aminated phenol polymer is contained in an amount, calculated as phosphorus, of about 1.0 to 200 mg, preferably about 5.0 to 150 mg, per unit weight of the ink.
[0121] The thickness of the corrosion-resistant film is not particularly limited, but is preferably about 1 nm to 20 μm, more preferably about 1 nm to 100 nm, and even more preferably about 1 nm to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the barrier layer and the heat-sealable resin layer. The thickness of the corrosion-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy. Analysis of the composition of the corrosion-resistant film using time-of-flight secondary ion mass spectrometry can reveal that, for example, secondary ions consisting of Ce, P, and O (e.g., Ce2PO4 + , CePO4 - At least one of the following: CrPO2 + , CrPO4 - Peaks derived from at least one of the above are detected.
[0122] The chemical conversion treatment is carried out by applying a solution containing a compound used for forming a corrosion-resistant film to the surface of the aluminum alloy foil by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the aluminum alloy foil so that the temperature of the aluminum alloy foil is about 70 to 200 ° C. In addition, before applying the chemical conversion treatment to the aluminum alloy foil, the aluminum alloy foil may be subjected to a degreasing treatment by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this way, it is possible to carry out the chemical conversion treatment of the surface of the aluminum alloy foil more efficiently. In addition, by using an acid degreasing agent in which a fluorine-containing compound is dissolved in an inorganic acid for the degreasing treatment, it is possible to form a fluoride of the metal that is a passive state as well as to degrease the metal foil, and in such a case, only the degreasing treatment may be carried out.
[0123] <1-1-5. Heat-fusible resin layer> In the exterior member 101, the heat-sealable resin layer 101D corresponds to the innermost layer, and is a layer (sealant layer) that exhibits the function of sealing the electrode body 200 by heat-sealing the heat-sealable resin layers 101D to each other when the electricity storage device 10 is assembled.
[0124] The resin constituting the heat-sealable resin layer 101D is not particularly limited as long as it is heat-sealable, but is preferably a resin containing a polyolefin skeleton, such as polyolefin or acid-modified polyolefin. The resin constituting the heat-sealable resin layer 101D can be analyzed to determine whether it contains a polyolefin skeleton, for example, by infrared spectroscopy, gas chromatography mass spectrometry, or the like. In addition, when the resin constituting the heat-sealable resin layer 101D is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, peaks derived from maleic anhydride are detected near wavenumber 1760 cm-1 and wavenumber 1780 cm-1. When the heat-sealable resin layer 101D is a layer composed of maleic anhydride-modified polyolefin, a peak derived from maleic anhydride is detected when measured by infrared spectroscopy. However, if the degree of acid modification is low, the peak may be small and not detected. In that case, it can be analyzed by nuclear magnetic resonance spectroscopy.
[0125] Specific examples of polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); propylene-α-olefin copolymers; and ethylene-butene-propylene terpolymers. Among these, polypropylene is preferred. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more.
[0126] The polyolefin may be a cyclic polyolefin. The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, styrene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; and cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these, cyclic alkenes are preferred, and norbornene is more preferred.
[0127] The acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of a polyolefin with an acid component. Polyolefins, copolymers of the above polyolefins with polar molecules such as acrylic acid or methacrylic acid, or polymers such as crosslinked polyolefins can also be used. Examples of the acid component used for the acid modification include carboxylic acids or anhydrides such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.
[0128] The acid-modified polyolefin may be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin by replacing it with an acid component, or by block-polymerizing or graft-polymerizing an acid component to the cyclic polyolefin. The cyclic polyolefin to be acid-modified is the same as described above. The acid component used for the acid modification is the same as the acid component used for the modification of the polyolefin.
[0129] Preferred acid-modified polyolefins include polyolefins modified with a carboxylic acid or anhydride thereof, polypropylenes modified with a carboxylic acid or anhydride thereof, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.
[0130] The thermally adhesive resin layer 101D may be formed of one type of resin alone, or may be formed of a blend polymer of two or more types of resins. Furthermore, the thermally adhesive resin layer 101D may be formed of only one layer, or may be formed of two or more layers of the same or different resins.
[0131] Furthermore, the thermally adhesive resin layer 101D may contain a lubricant, etc., if necessary. When the thermally adhesive resin layer 101D contains a lubricant, the conformability of the exterior member at the corners of the exterior member 101 can be improved. The lubricant is not particularly limited, and a known lubricant can be used. The lubricant may be used alone or in combination of two or more kinds.
[0132] The lubricant is not particularly limited, but preferably includes an amide-based lubricant. Specific examples of the lubricant include those exemplified for the base layer 101A. The lubricant may be used alone or in combination of two or more kinds.
[0133] When a lubricant is present on the surface of the heat-sealable resin layer 101D, the amount thereof is not particularly limited, but from the viewpoint of improving the conformability of the exterior component at corners and the like of the exterior component 101, it is preferably about 10 to 50 mg / m2, and more preferably about 15 to 40 mg / m2.
[0134] The lubricant present on the surface of the heat-fusible resin layer 101D may be a lubricant exuded from the resin constituting the heat-fusible resin layer 101D, or a lubricant applied to the surface of the heat-fusible resin layer 101D.
[0135] The thickness of the heat-sealable resin layer 101D is not particularly limited as long as the heat-sealable resin layers are heat-sealed to each other to seal the electricity storage device element, and may be, for example, about 100 μm or less, preferably about 85 μm or less, and more preferably about 15 to 85 μm. For example, when the thickness of the adhesive layer 101E described below is 10 μm or more, the thickness of the heat-sealable resin layer 101D is preferably about 85 μm or less, and more preferably about 15 to 45 μm. For example, when the thickness of the adhesive layer 101E described below is less than 10 μm or when the adhesive layer 101E is not provided, the thickness of the heat-sealable resin layer 101D is preferably about 20 μm or more, and more preferably about 35 to 85 μm.
[0136] <1-1-6.Adhesive layer> In the exterior member 101, the adhesive layer 101E is a layer that is provided, if necessary, between the barrier layer 101C (or the acid-resistant film) and the heat-sealable resin layer 101D in order to firmly bond them together.
[0137] The adhesive layer 101E is formed of a resin capable of bonding the barrier layer 101C and the thermally adhesive resin layer 101D. The adhesive layer 101E is preferably formed of a cured product of a resin composition containing a curable resin. The curable resin means a resin having a curing property such as a thermosetting resin or an ionizing radiation curable resin, and does not have a clear melting peak temperature after curing. For example, the same adhesive as exemplified for the adhesive layer 101B can be used as the resin used to form the adhesive layer 101E. The resin used to form the adhesive layer 101E preferably contains a polyolefin skeleton, and examples of the resin include the polyolefin and acid-modified polyolefin exemplified for the thermally adhesive resin layer 101D described above. The resin constituting the adhesive layer 101E can be analyzed to determine whether it contains a polyolefin skeleton, for example, by infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. In addition, when the resin constituting the adhesive layer 101E is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride modified polyolefin is measured by infrared spectroscopy, the wave number is 1760 cm-1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.
[0138] From the viewpoint of firmly adhering the barrier layer 101C and the thermally adhesive resin layer 101D, the adhesive layer 101E preferably contains an acid-modified polyolefin. Particularly preferred examples of the acid-modified polyolefin include polyolefins modified with carboxylic acids or their anhydrides, polypropylenes modified with carboxylic acids or their anhydrides, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.
[0139] Furthermore, from the viewpoint of making the exterior member 101 thin and having excellent shape stability after molding, the adhesive layer 101E is more preferably a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. In this case, the acid-modified polyolefin and the curing agent constitute a curable resin. As the acid-modified polyolefin, the above-mentioned ones can be preferably exemplified.
[0140] Moreover, the adhesive layer 101E is preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group and a compound having an epoxy group. Moreover, the adhesive layer 101E preferably contains at least one selected from the group consisting of polyurethane, polyester, and epoxy resin, and more preferably contains polyurethane and epoxy resin. As the polyester, for example, an amide ester resin is preferable. Amide ester resin is generally produced by the reaction of a carboxyl group and an oxazoline group. The adhesive layer 101E is more preferably a cured product of a resin composition containing at least one of these resins and the acid-modified polyolefin. In addition, if unreacted compounds such as a compound having an isocyanate group, a compound having an oxazoline group, or a curing agent such as an epoxy resin remain in the adhesive layer 101E, the presence of the unreacted compounds can be confirmed by a method selected from, for example, infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.
[0141] In addition, from the viewpoint of further increasing the adhesion between the barrier layer 101C and the adhesive layer 101E, the adhesive layer 101E is preferably a cured product of a resin composition containing a curing agent having at least one selected from the group consisting of an oxygen atom, a heterocycle, a C=N bond, and a COC bond. Examples of the curing agent having a heterocycle include a curing agent having an oxazoline group and a curing agent having an epoxy group. Examples of the curing agent having a C=N bond include a curing agent having an oxazoline group and a curing agent having an isocyanate group. Examples of the curing agent having a COC bond include a curing agent having an oxazoline group, a curing agent having an epoxy group, and polyurethane. It can be confirmed that the adhesive layer 101E is a cured product of a resin composition containing these curing agents by, for example, gas chromatography mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS), or other methods.
[0142] The compound having an isocyanate group is not particularly limited, but from the viewpoint of effectively increasing the adhesion between the barrier layer 101C and the adhesive layer 101E, a polyfunctional isocyanate compound is preferably used. The polyfunctional isocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of polyfunctional isocyanate-based curing agents include pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers. In addition, adducts, biuret products, isocyanurates, etc. are also included.
[0143] The content of the compound having an isocyanate group in the resin composition constituting the adhesive layer 101E is preferably in the range of 0.1 to 50% by mass, and more preferably in the range of 0.5 to 40% by mass, thereby effectively improving the adhesion between the barrier layer 101C and the adhesive layer 101E.
[0144] The compound having an oxazoline group is not particularly limited as long as it is a compound having an oxazoline skeleton. Specific examples of the compound having an oxazoline group include those having a polystyrene main chain and those having an acrylic main chain. In addition, examples of commercially available products include the Epocross series manufactured by Nippon Shokubai Co., Ltd.
[0145] The proportion of the compound having an oxazoline group in the resin composition constituting the adhesive layer 101E is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, which can effectively improve the adhesion between the barrier layer 101C and the adhesive layer 101E.
[0146] An example of a compound having an epoxy group is an epoxy resin. The epoxy resin is not particularly limited as long as it is a resin capable of forming a crosslinked structure by the epoxy group present in the molecule, and a known epoxy resin can be used. The weight average molecular weight of the epoxy resin is preferably about 50 to 2000, more preferably about 100 to 1000, and further preferably about 200 to 800. In the first disclosure, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under conditions using polystyrene as a standard sample.
[0147] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, polyglycerin polyglycidyl ether, etc. The epoxy resins may be used alone or in combination of two or more.
[0148] The ratio of the epoxy resin in the adhesive layer 101E is preferably in the range of 0.1 to 50% by mass, and more preferably in the range of 0.5 to 40% by mass, in the resin composition constituting the adhesive layer 101E, which can effectively improve the adhesion between the barrier layer 101C and the adhesive layer 101E.
[0149] The polyurethane is not particularly limited, and any known polyurethane can be used. The adhesive layer 101E may be, for example, a cured product of two-component curing polyurethane.
[0150] The proportion of polyurethane in the resin composition constituting the adhesive layer 101E is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, which can effectively improve the adhesion between the barrier layer 101C and the adhesive layer 101E in an atmosphere containing a component that induces corrosion of the barrier layer, such as an electrolyte solution.
[0151] In addition, when the adhesive layer 101E is a cured product of a resin composition containing at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and an epoxy resin, and the acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group, and the compound having an epoxy group each function as a curing agent.
[0152] The upper limit of the thickness of the adhesive layer 101E is preferably about 50 μm or less, about 40 μm or less, about 30 μm or less, about 20 μm or less, and about 5 μm or less, and the lower limit is preferably about 0.1 μm or more, and about 0.5 μm or more, and the thickness range is preferably about 0.1 to 50 μm, about 0.1 to 40 μm, about 0.1 to 30 μm, about 0.1 to 20 μm, about 0.1 to 5 μm, about 0.5 to 50 μm, about 0.5 to 40 μm, about 0.5 to 30 μm, about 0.5 to 20 μm, and about 0.5 to 5 μm. More specifically, in the case of the adhesive layer 101B or a cured product of an acid-modified polyolefin and a curing agent, the thickness is preferably about 1 to 10 μm, and more preferably about 1 to 5 μm. In addition, when the resin exemplified for the thermally adhesive resin layer 101D is used, the thickness is preferably about 2 to 50 μm, more preferably about 10 to 40 μm. In addition, when the adhesive layer 101E is an adhesive exemplified for the adhesive layer 101B or a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 101E can be formed, for example, by applying the resin composition and curing it by heating or the like. In addition, when the resin exemplified for the thermally adhesive resin layer 101D is used, the thermally adhesive resin layer 101D and the adhesive layer 101E can be formed, for example, by extrusion molding.
[0153] <1-1-7.Surface coating layer 101F> The exterior member 101 may have a surface coating layer 101F on the base material layer 101A (the side of the base material layer 101A opposite to the barrier layer 101C) as necessary for the purpose of improving at least one of design, electrolyte resistance, scratch resistance, conformability of the exterior member at corners, etc. The surface coating layer 101F is a layer located on the outermost layer side of the exterior member 101 when an electricity storage device is assembled using the exterior member 101.
[0154] The surface coating layer 101F can be formed from a resin such as polyvinylidene chloride, polyester, polyurethane, acrylic resin, or epoxy resin.
[0155] When the resin forming the surface coating layer 101F is a curable resin, the resin may be either a one-component curable type or a two-component curable type, but is preferably a two-component curable type. Examples of two-component curable resins include two-component curable polyurethane, two-component curable polyester, and two-component curable epoxy resin. Among these, two-component curable polyurethane is preferred.
[0156] Examples of two-component curing polyurethane include polyurethane containing a base material containing a polyol compound and a curing agent containing an isocyanate compound. Preferably, two-component curing polyurethane is used in which a polyol such as polyester polyol, polyether polyol, or acrylic polyol is used as a base material, and an aromatic or aliphatic polyisocyanate is used as a curing agent. In addition, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the hydroxyl group at the end of the repeating unit as the polyol compound. Since the surface coating layer 101F is formed of polyurethane, the exterior member 101 is provided with excellent electrolyte resistance.
[0157] The surface coating layer 101F may contain additives such as the above-mentioned lubricant, antiblocking agent, matting agent, flame retardant, antioxidant, tackifier, and antistatic agent in at least one of the surface and the inside of the surface coating layer 101F, as necessary, depending on the functionality to be provided to the surface of the surface coating layer 101F. Examples of the additives include fine particles having an average particle size of about 0.5 nm to 5 μm. The average particle size of the additive is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0158] The additive may be either an inorganic substance or an organic substance. The shape of the additive is not particularly limited, and examples thereof include a spherical, fibrous, plate-like, amorphous, and scaly shape.
[0159] Specific examples of additives include talc, silica, graphite, kaolin, montmorillonite, mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, alumina, carbon black, carbon nanotubes, high melting point nylon, acrylate resin, crosslinked acrylic, crosslinked styrene, crosslinked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. The additives may be used alone or in combination of two or more. Among these additives, silica, barium sulfate, and titanium oxide are preferable from the viewpoint of dispersion stability and cost. In addition, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment.
[0160] The method for forming the surface coating layer 101F is not particularly limited, and examples thereof include a method for applying a resin for forming the surface coating layer 101F. When an additive is added to the surface coating layer 101F, a resin mixed with the additive may be applied.
[0161] The thickness of the surface coating layer 101F is not particularly limited as long as the surface coating layer 101F exhibits the above-mentioned functions, and may be, for example, about 0.5 to 10 μm, and preferably about 1 to 5 μm.
[0162] <1-1-8. Manufacturing method of exterior components> The method for producing the exterior member 101 is not particularly limited as long as a laminate is obtained by laminating the layers of the exterior member 101 of this embodiment, and examples thereof include a method including a step of laminating at least the base layer 101A, the barrier layer 101C, and the thermally adhesive resin layer 101D in this order. As described above, an aluminum alloy foil having the above-mentioned predetermined composition can be used as the barrier layer 101C.
[0163] An example of a method for manufacturing the exterior member 101 of this embodiment is as follows. First, a laminate (hereinafter, sometimes referred to as "laminate A") is formed in which the base layer 101A, the adhesive layer 101B, and the barrier layer 101C are laminated in this order. Specifically, the laminate A can be formed by a dry lamination method in which an adhesive used for forming the adhesive layer 101B is applied to the base layer 101A or to the barrier layer 101C, the surface of which has been chemically treated as necessary, by a coating method such as gravure coating or roll coating, and then dried, and the barrier layer 101C or the base layer 101A is laminated thereon to cure the adhesive layer 101B.
[0164] Next, the thermally adhesive resin layer 101D is laminated on the barrier layer 101C of the laminate A. When the thermally adhesive resin layer 101D is directly laminated on the barrier layer 101C, the thermally adhesive resin layer 101D may be laminated on the barrier layer 101C of the laminate A by a method such as thermal lamination or extrusion lamination. In addition, when the adhesive layer 101E is provided between the barrier layer 101C and the heat-sealable resin layer 101D, for example, (1) a method of laminating the adhesive layer 101E and the heat-sealable resin layer 101D by extruding them on the barrier layer 101C of the laminate A (co-extrusion lamination method, tandem lamination method), (2) a method of separately forming a laminate in which the adhesive layer 101E and the heat-sealable resin layer 101D are laminated, and laminating this on the barrier layer 101C of the laminate A by a thermal lamination method, or a method of forming a laminate in which the adhesive layer 101E is laminated on the barrier layer 101C of the laminate A, and laminating this on the heat-sealable resin layer 101D by a thermal lamination method. (3) a method in which a molten adhesive layer 101E is poured between the barrier layer 101C of the laminate A and the heat-sealable resin layer 101D previously formed into a sheet-like film, and the laminate A and the heat-sealable resin layer 101D are bonded together via the adhesive layer 101E (sandwich lamination method); (4) a method in which an adhesive for forming the adhesive layer 101E is solution-coated on the barrier layer 101C of the laminate A, and then laminated by drying or baking, and the heat-sealable resin layer 101D previously formed into a sheet-like film is laminated on the adhesive layer 101E.
[0165] When the surface coating layer 101F is provided, the surface coating layer 101F is laminated on the surface of the base layer 101A opposite to the barrier layer 101C. The surface coating layer 101F can be formed, for example, by applying the above-mentioned resin forming the surface coating layer 101F to the surface of the base layer 101A. The order of the step of laminating the barrier layer 101C on the surface of the base layer 101A and the step of laminating the surface coating layer 101F on the surface of the base layer 101A is not particularly limited. For example, after forming the surface coating layer 101F on the surface of the base layer 101A, the barrier layer 101C may be formed on the surface of the base layer 101A opposite to the surface coating layer 101F.
[0166] As described above, a laminate is formed which includes, in this order, optional surface coating layer 101F / substrate layer 101A / optional adhesive layer 101B / barrier layer 101C / optional adhesive layer 101E / thermally adhesive resin layer 101D. In order to strengthen the adhesion of optional adhesive layer 101B and adhesive layer 101E, the laminate may be further subjected to a heat treatment.
[0167] In the exterior member 101, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary to improve the processability. For example, by subjecting the surface of the base material layer 101A opposite to the barrier layer 101C to corona treatment, the printability of the ink on the surface of the base material layer 101A can be improved.
[0168] It is preferable that the exterior member 101 has one or more layers having a buffer function (hereinafter referred to as "buffer layer") outside the thermally adhesive resin layer 101D, more preferably outside the barrier layer 101C. The buffer layer may be laminated on the outside of the base layer 101A, or the base layer 101A may also function as a buffer layer. When the exterior member 101 has multiple buffer layers, the multiple buffer layers may be adjacent to each other, or may be laminated via the base layer 101A, the barrier layer 101C, etc.
[0169] The material constituting the buffer layer can be arbitrarily selected from materials having cushioning properties. The material having cushioning properties is, for example, rubber, nonwoven fabric, or foam sheet. The rubber is, for example, natural rubber, fluororubber, or silicone rubber. The rubber hardness is preferably about 20 to 90. The material constituting the nonwoven fabric is preferably a material having excellent heat resistance. When the buffer layer is made of nonwoven fabric, the lower limit of the thickness of the buffer layer is preferably 100 μm, more preferably 200 μm, and more preferably 1000 μm. When the buffer layer is made of nonwoven fabric, the upper limit of the thickness of the buffer layer is preferably 5000 μm, and more preferably 3000 μm. The thickness of the buffer layer is preferably in the range of 100 μm to 5000 μm, 100 μm to 3000 μm, 200 μm to 3000 μm, 1000 μm to 5000 μm, or 1000 μm to 3000 μm. Among these, the thickness of the buffer layer is most preferably in the range of 1000 μm to 3000 μm.
[0170] When the buffer layer is made of rubber, the lower limit of the thickness of the buffer layer is preferably 0.5 mm. When the buffer layer is made of rubber, the upper limit of the thickness of the buffer layer is preferably 10 mm, more preferably 5 mm, and more preferably 2 mm. When the buffer layer is made of rubber, the preferred range of the thickness of the buffer layer is 0.5 mm to 10 mm, 0.5 mm to 5 mm, or 0.5 mm to 2 mm.
[0171] When the exterior member 101 has a buffer layer, the buffer layer functions as a cushion, thereby preventing the exterior member 101 from being damaged by impact when the energy storage device 10 is dropped or by handling during the manufacture of the energy storage device 10.
[0172] 4 is a side view of the electrode body 200 wrapped with the exterior member 101 during the manufacture of the electricity storage device 10. As shown in FIG. 4, the exterior member 101 is wrapped around the electrode body 200. In this case, the outermost layer of the electrode body 200 does not necessarily have to be an electrode, and may be, for example, a protective tape or a separator. With the exterior member 101 wrapped around the electrode body 200, the surfaces (thermally adhesive resin layers) of the exterior member 101 facing each other are heat sealed to form a first sealed portion 110.
[0173] In this embodiment, the root portion of the first sealing portion 110 is on a side 135 of the exterior body 100. The side 135 is formed at the boundary between the first surface 130 and the second surface 140, which has a smaller area than the first surface 130. In other words, the root portion of the first sealing portion 110 can be said to be formed at the boundary between the first surface 130 and the second surface 140, and not to be present on either the first surface 130 or the second surface 140. The root portion of the first sealing portion 110 may be present on the second surface 140. In the power storage device 10, the first sealing portion 110 is bent toward the second surface 140 around the side 135. In the power storage device 10, the first sealing portion 110 is in contact with the second surface 140 and covers substantially the entire second surface 140. The term "substantially the entire second surface 140" refers to a region that occupies 75% or more of the area of the second surface 140.
[0174] That is, in the electricity storage device 10, the first sealing portion 110 is not formed on the first surface 130 having a large area. The first surface 130 is flatter than when a sealing portion such as the first sealing portion 110 is in contact with the first surface 130. Therefore, even if another electricity storage device 10 is placed on the first surface 130, the other electricity storage device 10 does not tilt. As a result, according to the electricity storage device 10, when a plurality of electricity storage devices 10 are stacked, unevenness in the distribution of pressure applied to the lower electricity storage device 10 can be suppressed. In other words, when a module is formed by stacking a plurality of electricity storage devices 10, the first sealing portion 110 is not disposed on the surface (first surface 130) adjacent to the adjacent electricity storage device 10. In addition, such a configuration is preferable from the viewpoint that it is necessary to apply a high pressure uniformly from the outer surface of the battery in an all-solid-state battery to exhibit battery performance.
[0175] Furthermore, in the power storage device 10 of this embodiment, the root portion of the first sealing portion 110 is on the side 135 of the exterior body 100. Therefore, according to the power storage device 10, a wider bonding area can be secured in the first sealing portion 110 compared to when the root portion of the first sealing portion 110 is on the second surface 140 (for example, the central portion of the second surface 140 in the direction of the arrow UD). Note that the bonding area of the first sealing portion 110 does not necessarily need to be the entire area of the first sealing portion 110, and may be a part of the first sealing portion 110, such as only the vicinity of the root portion of the first sealing portion 110.
[0176] Moreover, in the power storage device 10, substantially the entire second surface 140 is covered by the first sealing portion 110. That is, in the power storage device 10, the length of the first sealing portion 110 in the direction of the arrow UD is longer than in the case where the first sealing portion 110 covers only half or less of the area of the second surface 140 (see FIG. 3). Therefore, according to the power storage device 10, a wide bonding area can be secured in the first sealing portion 110. Furthermore, since substantially the entire second surface 140 is covered by the first sealing portion 110, the power storage device 10 is stable even if the power storage device 10 is placed upright so that the second surface 140 contacts the mounting surface. That is, the power storage device 10 is unlikely to tilt with respect to the mounting surface. Therefore, such a configuration is effective, for example, when a plurality of power storage devices 10 are arranged side by side to form a module.
[0177] Fig. 5 is a view showing a state in which the exterior member 101 is wound around the electrode body 200 from below during the manufacture of the electricity storage device 10. As shown in Fig. 5, in the electricity storage device 10, the direction along the side 135 is the TD (Transverse Direction) of the exterior member 101, and the direction perpendicular to the side 135 is the MD (Machine Direction) of the exterior member 101. In other words, the direction along the side 135 is the direction (TD) perpendicular to the flow direction (MD) of the exterior member 101.
[0178] In the electricity storage device 10, the first sealing portion 110 is folded along the side 135, and the direction along the side 135 is a direction perpendicular to the flow direction of the exterior member 101. Therefore, according to the electricity storage device 10, even if a crease is formed in the direction perpendicular to the flow direction of the exterior member 101, the exterior member 101 is unlikely to break, and therefore it is possible to reduce the possibility that the first sealing portion 110 will break due to the folding of the first sealing portion 110.
[0179] The machine direction (MD) of the exterior member 101 corresponds to the rolling direction (RD) of the metal foil (aluminum alloy foil, etc.) of the barrier layer included in the exterior member 101. The TD of the exterior member 101 corresponds to the TD of the metal foil. The rolling direction (RD) of the metal foil can be determined by the rolling marks.
[0180] In addition, the sea-island structure can be confirmed by observing multiple cross sections of the heat-fusible resin layer of the exterior member 101 with an electron microscope, and the direction parallel to the cross section in which the average diameter of the islands in the direction perpendicular to the thickness direction of the heat-fusible resin layer (hereinafter also referred to as the "length direction of the heat-fusible resin layer") was maximum can be determined as the MD. When the MD of the exterior member 101 cannot be identified based on the rolling marks of the metal foil, the MD can be identified by this method.
[0181] Specifically, the sea-island structure is confirmed by observing the longitudinal cross section of the heat-sealable resin layer and each cross section (a total of 10 cross sections) at an angle of 10 degrees from the direction parallel to the longitudinal cross section and perpendicular to the longitudinal cross section. Next, for each island on each cross section, the island diameter d is measured by the linear distance connecting both ends in the direction perpendicular to the thickness direction of the heat-sealable resin layer. Next, the average of the diameters d of the top 20 largest islands is calculated for each cross section. The direction parallel to the cross section in which the average island diameter d was the largest is determined to be the MD.
[0182] Fig. 6 is a diagram that diagrammatically shows a part of the cross section taken along line VI-VI in Fig. 2. As shown in Fig. 6, second sealing portion 120 seals exterior body 100 in a state in which electrode terminal 300 is sandwiched between exterior body 100 and electrode terminal 300.
[0183] Fig. 7 is a diagram for explaining a method of forming the second sealed portion 120. As shown in Fig. 7, the exterior member 101 is folded, and the surfaces (thermally adhesive resin layers) of the exterior member 101 facing each other are heat-sealed to form the second sealed portion 120. Although omitted in Fig. 7, the electrode terminal 300 is located between the surfaces of the exterior member 101 facing each other. An adhesive film that adheres to both metal and resin may be disposed between the electrode terminal 300 and the exterior member 101.
[0184] 6 again, the electrode body 200 includes a plurality of electrodes 210 (positive and negative electrodes). A current collector 215 extending from each electrode 210 is connected to an electrode terminal 300. In the electricity storage device 10, a portion of the electrode terminal 300 that is on the outside of the exterior body 100 is located at a position that is approximately half the thickness of the electricity storage device 10 in the thickness direction of the electricity storage device 10. In other words, the length L2 is approximately half the length L1. Note that "approximately half the thickness of the electricity storage device 10" means 35% to 65% of the thickness of the electricity storage device 10.
[0185] Therefore, according to the energy storage device 10, for example, the difference between the longest distance and the shortest distance between each of the multiple electrodes 210 and the electrode terminal 300 can be made smaller compared to when the electrode terminal 300 is located at approximately the same position as the first surface 130 in the thickness direction of the energy storage device 10.
[0186] <1-2. Manufacturing method of energy storage device> Fig. 8 is a flowchart showing a manufacturing procedure of the power storage device 10. The steps shown in Fig. 8 are performed by a manufacturing apparatus for the power storage device 10, for example.
[0187] The manufacturing equipment wraps the exterior member 101 around the electrode body 200 (step S100). The manufacturing equipment forms the first sealed portion 110 by heat-sealing the mutually facing surfaces (thermally adhesive resin layers) of the exterior member 101 (step S110). This completes the unfinished product shown in Figs. 4 and 5.
[0188] The manufacturing equipment folds the first sealing portion 110 so that the first sealing portion 110 contacts the second surface 140 (step S120). The manufacturing equipment folds the exterior member 101 in a state in which the electrode body 200 is stored, and forms the second sealing portion 120 by heat-sealing the mutually facing surfaces (thermally adhesive resin layers) of the exterior member 101 (step S130). This completes the electricity storage device 10.
[0189] <1-3.Features> As described above, in the electricity storage device 10 according to the first embodiment, the first sealing portion 110 is folded toward the second surface 140 side having a smaller area. That is, the first sealing portion 110 does not exist on the first surface 130 having a larger area. Therefore, even if another electricity storage device 10 is placed on the first surface 130, the other electricity storage device 10 does not tilt. As a result, according to the electricity storage device 10, when a plurality of electricity storage devices 10 are stacked, unevenness in the distribution of pressure applied to the lower electricity storage device 10 can be suppressed. In addition, when used in an all-solid-state battery, it is necessary to apply a high pressure uniformly from the outer surface of the battery to exhibit the battery performance, so that the packaging form of the present invention is preferable. In addition, in the electricity storage device 10, the root portion of the first sealing portion 110 is on the side 135 of the exterior body 100. Therefore, according to the energy storage device 10, when the first sealing portion 110 is fitted onto the second surface 140, a wider bonding width can be ensured in the first sealing portion 110 compared to when the base portion of the first sealing portion 110 is located on the second surface 140.
[0190] [2. Second Embodiment] In the electricity storage device 10 according to the above-mentioned first embodiment, the second sealed portion 120 is formed by folding the exterior member 101 and heat-sealing the mutually facing surfaces of the exterior member 101. However, the shape and the method of forming the second sealed portion 120 are not limited thereto. Note that the following mainly describes the parts that are different from the first embodiment, and the description of the parts that are common to the first embodiment will be omitted.
[0191] <2-1. Configuration of the power storage device> Fig. 9 is a plan view typically showing an electricity storage device 10X according to the second embodiment, Fig. 10 is a side view typically showing an electricity storage device 10X, and Fig. 11 is a perspective view typically showing a lid 400.
[0192] 9, 10, and 11, the exterior body 100X is formed by fitting a lid body 400 into each of the openings at both ends of an exterior member 101 wrapped around an electrode assembly 200. With the lid body 400 fitted in, the exterior member 101 and the lid body 400 are heat-sealed to form a second sealed portion 120X.
[0193] The lid body 400 is a bottomed tray-like member having a rectangular shape in a plan view, and is formed by, for example, cold forming the exterior member 101. The lid body 400 does not necessarily have to be made of the exterior member 101, and may be a metal molded product or a resin molded product. In the power storage device 10X, the lid body 400 is arranged so that the bottom side of the lid body 400 is located inside the exterior body 100X. In the power storage device 10X, the bottom side of the lid body 400 does not necessarily have to be located inside the exterior body 100X. In the power storage device 10X, the bottom side of the lid body 400 may be located outside the exterior body 100X.
[0194] In addition, when the electrode body 200 is stored, the electrode terminal 300 passes between the lid body 400 and the exterior member 101 and protrudes to the outside of the exterior body 100X. That is, the lid body 400 and the exterior member 101 are heat sealed with the electrode terminal 300 sandwiched between them. In the power storage device 10X, the position where the electrode terminal 300 protrudes to the outside does not necessarily have to be between the lid body 400 and the exterior member 101. For example, the electrode terminal 300 may protrude to the outside from a hole formed on any one of the six surfaces of the exterior body 100X. In this case, a small gap between the exterior body 100X and the electrode terminal 300 is filled with, for example, resin.
[0195] Furthermore, in the power storage device 10X, the lid body 400 and the electrode terminal 300 are provided as separate bodies. However, the lid body 400 and the electrode terminal 300 do not necessarily have to be provided as separate bodies. For example, the lid body 400 and the electrode terminal 300 may be formed integrally.
[0196] Fig. 12 is a diagram showing a first example in which the lid body 400 and the electrode terminal 300 are integrally formed. As shown in Fig. 12, in the first example, the electrode terminal 300 is heat-sealed in advance to the side surface of the lid body 400. Note that, for example, when the lid body 400 is made of an exterior member 101, an adhesive film that adheres to both metal and resin may be disposed between the lid body 400 and the electrode terminal 300.
[0197] Fig. 13 is a diagram showing a second example in which the lid 400 and the electrode terminal 300 are integrally formed. As shown in Fig. 13, in the second example, the electrode terminal 300 passes through a hole formed in the bottom surface portion of the lid 400. A small gap in the hole in the bottom surface of the lid 400 is filled with, for example, resin.
[0198] Furthermore, in the power storage device 10X, a gas valve may be attached to a hole formed in the second sealing portion 120X or any one of six faces of the exterior body 100X. The gas valve is configured, for example, as a check valve or a breaker valve, and is configured to reduce the pressure inside the exterior body 100X when the pressure increases due to gas generated inside the power storage device 10X.
[0199] <2-2. Manufacturing method of electricity storage device> Fig. 14 is a flowchart showing a manufacturing procedure for the power storage device 10X. The steps shown in Fig. 14 are performed, for example, by a manufacturing apparatus for the power storage device 10X.
[0200] The manufacturing equipment wraps the exterior member 101 around the electrode body 200 (step S200). The manufacturing equipment forms the first sealed portion 110 by heat-sealing the mutually facing surfaces (thermally adhesive resin layers) of the exterior member 101 (step S210). This completes the unfinished product shown in Figs. 4 and 5.
[0201] The manufacturing equipment bends the first sealing portion 110 so that the first sealing portion 110 contacts the second surface 140 (step S220). The manufacturing equipment houses the electrode body 200 in the unfinished product produced in step S220 and attaches the lid body 400 to each of the openings at both ends (step S230). The manufacturing equipment forms the second sealing portion 120X by heat-sealing the exterior member 101 and the lid body 400 (step S240). This completes the electricity storage device 10X.
[0202] <2-3.Features> In the power storage device 10X according to the second embodiment, the first sealing portion 110 is also bent toward the second surface 140 having the smaller area. Therefore, according to the power storage device 10X, when a plurality of power storage devices 10X are stacked, unevenness in the distribution of pressure applied to the lower power storage device 10X can be suppressed.
[0203] <2-4.Other features> In the power storage device 10X according to the second embodiment, the first sealing unit 110 does not necessarily have to be bent towards the second surface 140 having a smaller area. For example, the first sealing unit 110 may be bent towards the first surface 130 having a larger area. Furthermore, the root portion of the first sealing unit 110 does not necessarily have to be on the side 135 of the exterior body 100X. The root portion of the first sealing unit 110 may be located on a surface of the exterior body 100X other than the lid body 400, for example. Even in this case, the power storage device 10X according to the second embodiment includes, for example, the following features.
[0204] The energy storage device 10X comprises an electrode body (electrode body 200) and an exterior body (exterior body 100X) that seals the electrode body (electrode body 200). The exterior body (exterior body 100X) is wrapped around the electrode body (electrode body 200) and comprises an exterior member (exterior member 101) having openings formed at both ends, and a lid body (lid body 400) that seals the openings.
[0205] In the electricity storage device 10X, the second sealed portion 120X is not formed by heat sealing mutually facing surfaces of the exterior member 101 as in the first embodiment (see FIG. 7). In the electricity storage device 10X, the opening of the exterior member 101 wrapped around the electrode body 200 is sealed by the lid body 400. That is, the second sealed portion 120X is formed in the portion where the lid body 400 and the exterior member 101 overlap (see FIGS. 9 and 10). With this configuration, the area of the second sealed portion 120X can be easily narrowed by adjusting the depth L3 (FIG. 11) of the lid body 400.
[0206] Furthermore, in the electricity storage device 10X, at a position of the exterior member 101 that covers the corner C1 (FIGS. 9 and 10) of the electrode body 200, no excessive load is generated due to the corner C1 piercing the exterior member 101. This is because, as described above, in the electricity storage device 10X, the second sealed portion 120X is not formed by heat sealing mutually facing surfaces of the exterior member 101 as in the first embodiment.
[0207] Furthermore, the manufacturing procedure of the power storage device 10X is not limited to the procedure shown in the flowchart of Fig. 14. For example, the power storage device 10X may be manufactured according to the procedure shown in the flowchart of Fig. 15.
[0208] FIG. 15 is a flowchart showing another manufacturing procedure of the power storage device 10X according to the second embodiment. The steps shown in FIG. 15 are performed, for example, by a manufacturing apparatus for the power storage device 10X. The manufacturing apparatus attaches a member (for example, a member shown in FIGS. 12 and 13) in which the electrode terminal 300 and the lid body 400 are integrated to the electrode body 200 (step S250). For example, the electrode terminal 300 is welded to the electrode body 200. Thereafter, the manufacturing apparatus wraps the exterior member 101 around the electrode body 200 (step S260). The manufacturing apparatus forms the first sealed portion 110 by heat-sealing the mutually facing surfaces (thermally adhesive resin layers) of the exterior member 101, and forms the second sealed portion 120X by heat-sealing the exterior member 101 and the lid body 400 together (step S270). This completes the power storage device 10X. The power storage device 10X may be manufactured by such a procedure.
[0209] [3. Embodiment 3] In a battery manufacturing process, a temporarily sealed electricity storage device is generally subjected to a process of aging in a predetermined temperature environment for a predetermined time for the purpose of permeating an electrolyte into the electrode body (hereinafter referred to as an aging process). In the aging process, gas is generated from the electrode body 200, and it is necessary to discharge the gas to the outside of the battery. In the electricity storage device 10X according to the above-mentioned second embodiment, no mechanism is provided for releasing the gas generated in the aging process in the final stage of manufacturing the electricity storage device 10X. In the electricity storage device 10Y according to the third embodiment, a mechanism is provided for releasing the gas generated from the electrode body 200 in the final stage of manufacturing the electricity storage device 10Y. In the following, differences from the second embodiment will be mainly described, and a description of the parts common to the second embodiment will be omitted.
[0210] <3-1. Configuration of the power storage device> Fig. 16 is a side view showing a state in which the exterior member 101Y is wrapped around the electrode body 200 during the manufacture of the electricity storage device 10Y. Fig. 17 is a bottom view showing a state in which the exterior member 101Y is wrapped around the electrode body 200 and a lid body 400 is attached to the exterior member 101Y during the manufacture of the electricity storage device 10Y.
[0211] As shown in Fig. 16 and Fig. 17, the piece 150 is formed in a state where the exterior member 101Y is wound around the electrode body 200. The piece 150 is formed by joining mutually facing surfaces of the exterior member 101Y in a state where the exterior member 101Y is wound around the electrode body 200. More specifically, the piece 150 is formed by joining (heat sealing) the peripheries of the mutually facing surfaces in a state where the exterior member 101Y is wound around the electrode body 200. That is, in the piece 150, a first sealed portion 154 is formed on the periphery.
[0212] Further, in the piece 150, a space 152 is formed where the opposing surfaces of the exterior member 101Y are not joined to each other. In the vicinity of the side 135, a joining region 151 where the opposing surfaces of the exterior member 101Y are joined to each other and an unjoined region 153 where the opposing surfaces of the exterior member 101Y are not joined to each other are arranged alternately. That is, in the piece 150, a pattern of the joining region 151 is formed along the side 135.
[0213] The gas generated from the electrode body 200 is discharged to the outside of the exterior body 100Y by releasing the sealed state of the exterior body 100Y, for example by cutting off a part of the piece 150. Note that the gas discharged to the outside of the exterior body 100Y here is not necessarily limited to the gas generated from the electrode body 200, and may be a gas other than the gas generated from the electrode body 200, such as air, water vapor, or hydrogen sulfide.
[0214] Thereafter, the portion including the vicinity of the side 135 is heat-sealed in a strip shape, thereby sealing the exterior body 100Y again. This completes the electricity storage device 10Y. In the completed electricity storage device 10Y, in the vicinity of the side 135, regions where the bonding strength between the mutually facing surfaces of the exterior member 101Y is strong and regions where the bonding strength between the surfaces is weak are alternately arranged along the side 135. In other words, in the heat-sealed portion in the vicinity of the side 135, thin portions and thick portions are alternately arranged along the side 135. This is because, by heat-sealing the vicinity of the side 135 again, the unbonded region 153 is single-sealed, but the bonded region 151 is double-sealed.
[0215] <3-2. Manufacturing method of electricity storage device> Fig. 18 is a flowchart showing a manufacturing procedure for the power storage device 10Y. The steps shown in Fig. 18 are performed, for example, by a manufacturing apparatus for the power storage device 10Y.
[0216] The manufacturing equipment wraps the exterior member 101Y around the electrode body 200 (step S300). The manufacturing equipment forms the first sealed portion 154 by heat-sealing the peripheral edges of the mutually facing surfaces (thermally adhesive resin layers) of the exterior member 101Y (step S310). The manufacturing equipment forms a pattern of the bonding region 151 by heat-sealing the mutually facing surfaces of the exterior member 101Y in the vicinity of the side 135 (step S320).
[0217] The manufacturing equipment attaches the lid body 400 to each of the openings at both ends with the electrode body 200 housed in the unfinished product produced in step S320 (step S330). The manufacturing equipment forms the second sealed portion 120X by heat-sealing the exterior member 101Y and the lid body 400 (step S340). Then, an aging process is performed.
[0218] The manufacturing equipment removes gas generated in the aging process by, for example, cutting off piece 150 (step S350). The manufacturing equipment reseals exterior body 100Y by heat-sealing a portion of piece 150 including bonding region 151 into a strip shape and removing the edge portion (step S360). Thereafter, piece 150 is folded toward second surface 140 to complete electricity storage device 10Y.
[0219] <3-3.Features> In the electricity storage device 10Y according to the third embodiment, the piece 150 including the first sealing portion 154 is also folded toward the second surface 140 having a smaller area. Therefore, according to the electricity storage device 10Y, when a plurality of electricity storage devices 10Y are stacked, unevenness in the distribution of pressure applied to the lower electricity storage device 10Y can be suppressed. When used in an all-solid-state battery, it is necessary to apply high pressure uniformly from the outer surface of the battery to exhibit battery performance, and therefore the packaging form of the present invention is preferable.
[0220] [4. Embodiment 4] In the power storage device 10X according to the above-described second embodiment, the position from which the electrode terminal 300 protrudes to the outside is between the lid body 400 and the exterior member 101. However, the position from which the electrode terminal 300 protrudes to the outside is not limited thereto. Note that the following description will focus on the parts that are different from the second embodiment, and a description of the parts that are common to the second embodiment will be omitted.
[0221] <4-1. Configuration of the power storage device> FIG. 19 is a plan view that typically shows an electricity storage device 10XA according to the fourth embodiment. FIG. 20 is a side view that typically shows the electricity storage device 10XA. The exterior body 100X of the electricity storage device 10XA includes a pair of long sides 100XA and a pair of short sides 100XB in a plan view. The exterior body 100X is configured by fitting a lid body 400 into each of the openings along the long sides 100XA of an exterior member 101 that is wrapped around the electrode body 200. With the lid body 400 fitted in, the exterior member 101 and the lid body 400 are heat-sealed to form a second sealed portion 120X. A through hole (not shown) is formed in the lid body 400. The two electrode terminals 300 protrude from the through holes of the lid body 400 to the outside of the exterior body 100X. The two electrode terminals 300 are shaped to fit along the long side 100XA of the exterior body 100X. Small gaps between the through holes and the electrode terminals 300 are filled with, for example, resin. In the fourth embodiment, the first sealing portion 110 is formed on one of the pair of short sides 100XB.
[0222] In the thickness direction (arrow UD direction) of the power storage device 10XA, the position from which the electrode terminal 300 of the lid body 400 protrudes can be selected arbitrarily. In the fourth embodiment, as shown in FIG. 20, the electrode terminal 300 protrudes from approximately the center of the lid body 400 to the outside of the exterior body 100X in the thickness direction of the power storage device 10XA. The length of the electrode terminal 300 in the depth direction (arrow FB direction) of the power storage device 10XA can be selected arbitrarily. In the fourth embodiment, the length of the electrode terminal 300 in the depth direction (arrow FB direction) of the power storage device 10XA is substantially the same as the length of the electrode body 200.
[0223] <4-2.Features> In the power storage device 10XA according to the fourth embodiment, the electrode terminals 300 are arranged along the long side 100XA that is longer in the depth direction, so that it is possible to use larger electrode terminals 300. This makes it possible to provide a high-output power storage device 10XA. EXAMPLES
[0224] The present embodiment will be described in detail below by showing electricity storage devices of examples and comparative examples, but the present embodiment is not limited to the examples.
[0225] An ingot of an aluminum alloy having each composition shown in Tables 1 and 2 (the balance being Al and other inevitable impurities) was prepared. The ingot was subjected to homogenization treatment under the conditions shown in Tables 1 and 2, and then hot-rolled to a finish temperature of 330°C to form a plate material having a thickness of 3 mm. Then, through cold rolling, intermediate annealing, final cold rolling, and final annealing, an aluminum alloy foil sample having a thickness of 40 μm and a width of 1200 mm was prepared. The conditions of the intermediate annealing and the final annealing are shown in Tables 1 and 2. In Example 11, CAL annealing was performed as the intermediate annealing. CAL was performed under the conditions of a heating rate of 70°C / sec, a heating temperature of 420°C, a holding time of 0 seconds, and a cooling rate of 50°C / sec. The cold rolling items in Tables 1 and 2 show the plate thickness immediately before the intermediate annealing and the cold rolling reduction ratio to the plate thickness. The following tests or measurements were performed on the exterior members including the prepared aluminum alloy foil, and the results are shown in Tables 1 to 4.
[0226] Tensile strength, elongation at break Both the tensile strength and the elongation at break were measured by a tensile test in accordance with JIS Z2241. In order to measure the elongation in the 0° direction relative to the rolling direction, a JIS No. 5 test piece was taken from the sample and the test was performed at a tensile speed of 2 mm / min using a universal tensile tester (Shimadzu Corporation AGS-X 10 kN).
[0227] The elongation was the elongation at break, and was calculated as follows. First, two lines were marked at the longitudinal center of the test piece in the perpendicular direction to the test piece, spaced 50 mm apart, which is the gauge length. After the test, the fracture surfaces of the aluminum alloy foils were butted together to measure the distance between the marks. The gauge length (50 mm) was subtracted from the distance between the marks to calculate the elongation (mm), and the elongation (%) was calculated by dividing the elongation by the gauge length (50 mm).
[0228] ·Average grain size The surface of the aluminum alloy foil was electrolytically polished at a voltage of 20 V using a mixed solution of 20% by volume perchloric acid and 80% by volume ethanol. It was then anodized in Barker's solution at a voltage of 30 V. After the anodization, the crystal grains of the specimen were observed under an optical microscope. The average crystal grain size was calculated from the photographs taken using the cutting method specified in JIS G0551.
[0229] · L1 (HAGB length) / L2 (LAGB length) The foil surface was electrolytically polished, and then the crystal orientation was analyzed using a SEM-EBSD device to observe high-angle grain boundaries (HAGBs) with a misorientation between crystal grains of 15° or more, and low-angle grain boundaries (LAGBs) with a misorientation between 2° or more and less than 15°. Measurements were performed in four fields of view with a field size of 170×340μm at a magnification of ×500, and the length of the HAGB (L1) and the length of the LAGB (L2) per unit area in the field of view were obtained, and the ratio between them was calculated. The calculated ratio is shown in Tables 3 and 4 as L1 / L2.
[0230] Crystal orientation Copper orientation is {112} <111> , R direction is {123} <634> was used as the representative orientation. The orientation density of each orientation was obtained by the following method. Incomplete pole figures of {111}, {200}, and {220} were measured using X-ray diffraction. The results were used to calculate the orientation distribution function (ODF) and obtain the orientation densities of the Copper orientation and R orientation.
[0231] ·Surface analysis The Mg concentration on the foil surface was estimated by XPS (X-ray Photoelectron Spectroscopy). In the surface area from the outermost surface to a depth of 8 nm, narrow spectra obtained by narrow scan measurement were subjected to waveform separation, and the atomic concentration of each element was quantified. The Mg amount was quantified using the Mg2p spectrum. The details of the analysis conditions are as follows. Measurement equipment: ULVAC-PHI PHI5000-VersaProbeIII Incident X-ray: Al Kα monochromatic X-ray, hν=1486.6ev X-ray source output: 100W, 20kV, 5.8mA Pass energy: 26 eV Step: 0.05eV Analysis area (beam diameter): 100μm x 1.4mm Detection angle: 45° Photoelectron capture angle: 45 degrees Measurement area: 100μφ, 1.4mm in the X direction Peak shift correction: Correct the C1s peak so that the CC peak is 285.0 eV Charge neutralization: Charge neutralization using dual beams of Ar ions and electron beams
[0232] Oxide film thickness measurement The oxide film thickness was measured using an FE-EPMA (Electron Probe Micro Analyzer) device. The oxide film thickness of the sample was calculated using a calibration curve of X-ray intensity obtained from an oxide film sample with a known thickness. The FE-EPMA device used was a JXA-8530F manufactured by JEOL Ltd. The analysis conditions were an accelerating voltage of 10 kV, a probe current of 100 nA, and a beam diameter of 50 μm.
[0233] -Puncture strength of aluminum alloy foil A needle with a diameter of 1.0 mm and a tip radius of 0.5 mm was pierced at a speed of 50 mm / min into an exterior component containing an aluminum alloy foil with a thickness of 40 μm, and the maximum load (N) until the needle penetrated the foil was measured as the piercing strength. A piercing strength of 9.0 N or more was judged to have good piercing resistance, and shown as "A" in Tables 3 and 4. A piercing strength of less than 9.0 N was judged to have poor piercing resistance, and shown as "C" in Tables 3 and 4.
[0234] -Evaluation of corrosion resistance to electrolyte Each aluminum alloy foil used in the examples and comparative examples was cut into a rectangle of 45 mm long x 15 mm wide. Next, a rectangular polyethylene film of 50 mm long x 20 mm wide was placed on the front and back surfaces of the aluminum alloy foil, and heat-welded to attach and cover the aluminum alloy foil so that an exposed portion of 1 cmφ was formed on one of the front and back surfaces of the aluminum alloy foil, to prepare a test sample. The corrosion resistance of the test sample was evaluated at the 1 cmφ portion where the aluminum alloy foil AL was exposed, and the end of the test sample that was not immersed in the electrolyte was exposed to connect to the working electrode. Next, the test sample AL was set as the working electrode, and metallic lithium Li (disk-shaped with a diameter of 15 mm x thickness of 0.35 mm) was set as the counter electrode, and the electrolyte (composed of 1 mol / l LiPF6 and a mixture of ethylene carbonate, diethyl carbonate, and dimethyl carbonate (volume ratio 1:1:1)) was immersed. In this state, a voltage of 0.1 V was applied for 1 hour in an environment of 20°C, and then the surface of the aluminum alloy foil was observed. Surfaces that were corroded, as shown in Figure 3F(B), were rated C, while surfaces that remained unchanged, as shown in Figure 3F(A), were rated A. The results are shown in Tables 3 and 4. It can be seen that compounds with lithium are formed on the corroded aluminum alloy foil surface, and the surface is raised due to volume expansion.
[0235] ·Corrosion resistance of aluminum alloy foil to solid electrolytes In a glove box, a solid electrolyte (Li2S-P2S5 (75:25)) with a thickness of 800 μm and a diameter of 10 mm was prepared by powder compaction. Next, an indium foil (thickness 0.3 mm to diameter 9 mm), a lithium foil (thickness 0.2 mm to diameter 8 mm), and an indium foil (thickness 0.1 mm to diameter 9 mm) were placed on the solid electrolyte so that the indium foil (thickness 0.1 mm) was on the solid electrolyte side, and the foil was restrained and left overnight. After that, the restraint was released, and each aluminum alloy foil used in the examples and comparative examples was punched out to a diameter of 9 mm and laminated on the solid electrolyte on the opposite side of the foil. The obtained laminate was restrained and sealed in a glass cell with leads. The laminate was taken out of the glove box and left for 1 hour to stabilize. In this state, a voltage of -0.53 V was applied for 3 hours or 10 hours in an environment of 25 ° C., and then the amount of electricity per unit area was calculated. The amount of electricity was 4 C / cm 2 If it is less than 4C / cm, it is rated A. 2 If it is 4C / cm, it is rated B. 2 When the value was greater than 1, it was rated as C. The results are shown in Tables 3 and 4.
[0236] -Evaluation of exterior material conformity Each exterior member obtained above was cut into a square of length (MD) 100 mm x width (TD) 100 mm to prepare a test sample. This test sample was folded in half at the center of the width direction so that the heat-sealed resin layer was on the inside, to prepare a rectangular folded sample of length (MD) 100 mm x width (TD) 50 mm. This folded sample was sandwiched between two metal plates of width 200 mm x length 200 mm x thickness 15 mm parallel to the width (TD) direction at the center of the length (MD). The sandwiched sample was folded back and forth at 180 degrees left and right, and the number of times it was folded back and forth until cracks appeared in the aluminum was measured. The cracks were confirmed by shining light from an LED light. The evaluation was performed N=5 times and the average value was calculated. The number of times that cracks appeared was 10 or more was evaluated as A, and the number of times that cracks appeared less than 10 was evaluated as C. The results are shown in Tables 3 and 4.
[0237] -Puncture strength of exterior materials The puncture strength of each of the exterior components obtained above was measured from the base layer side by a method conforming to the provisions of JIS Z1707:1997. Specifically, in a measurement environment of 23±2°C and relative humidity (50±5)%, a test piece was fixed with a 115mm diameter table with a 15mm opening in the center and a presser plate, and a semicircular needle with a diameter of 1.0mm and a tip radius of 0.5mm was pierced at a speed of 50±5mm per minute, and the maximum stress until the needle penetrated was measured. The number of test pieces was 5, and the average value was calculated. If the number of test pieces was insufficient to measure 5, the number that could be measured was measured and the average value was calculated. The puncture strength was measured using Imada's ZP-50N (force gauge) and MX2-500N (measurement stand). The results are shown in Tables 3 and 4. When the puncture strength was 30N or more, it was evaluated as A, and when it was 30N or less, it was evaluated as C. The results are shown in Tables 3 and 4.
[0238] [Table 1]
[0239] [Table 2]
[0240] [Table 3]
[0241] [Table 4]
[0242] <Manufacture of exterior components> A laminated film was prepared as a substrate layer, in which a polyethylene terephthalate film (12 μm) / adhesive layer (two-component curing urethane adhesive (polyol compound and aromatic isocyanate compound), thickness 3 μm) / biaxially oriented nylon film (thickness 15 μm) were laminated in this order. Next, a barrier layer made of the above-mentioned aluminum alloy foil (having the composition in Tables 1 and 2 and the properties in Tables 3 and 4, thickness 40 μm) with acid-resistant films formed on both sides was laminated by a dry lamination method on the biaxially oriented nylon film (thickness 15 μm) of the substrate layer. Specifically, acid-resistant films (films formed by chromate treatment, with a chromium content of 30 mg / m) were formed on both sides. 2 A two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil on which the adhesive layer (thickness after curing: 3 μm) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of a base layer / adhesive layer / barrier layer. Next, on the barrier layer of the obtained laminate, maleic anhydride-modified polypropylene (thickness: 40 μm) as an adhesive layer and polypropylene (thickness: 40 μm) as a heat-sealable resin layer were co-extruded, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior member in which a polyethylene terephthalate film (12 μm) / adhesive layer (3 μm) / biaxially oriented nylon film (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / heat-sealable resin layer (40 μm) were laminated in this order.
[0243] Incidentally, erucic acid amide was present as a lubricant on both sides of the exterior member to form a lubricant layer.
[0244] The exterior members of the electricity storage devices of Examples 1 to 15 and 22 to 40 are each composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, and the barrier layer contains an aluminum alloy foil that satisfies the composition of Fe: 0.2% by mass to 2.0% by mass and Mg: 0.1% by mass to 5.0% by mass. The exterior members of Examples 1 to 15 and 22 to 40 have excellent conformability of the exterior member at corners and the like, effectively suppress corrosion of the aluminum alloy foil when current is passed through the exterior member with the electrolyte attached, and further have high mechanical strength.
[0245] [5. Modifications] Although the embodiments 1 to 4 have been described above, the present invention is not limited to the above embodiments 1 to 4, and various modifications are possible without departing from the spirit of the present invention. Modifications will be described below.
[0246] <5-1> In the above-mentioned embodiments 1-4, one exterior member is wound around the electrode assembly 200. However, it is not necessary to wind one exterior member around the electrode assembly 200. For example, two or more exterior members may be wound around the electrode assembly 200.
[0247] FIG. 21 is a side view showing a state in which the exterior members 101Z1 and 101Z2 are wound around the electrode body 200 during the manufacturing process of the electric storage device in the modified example. As shown in FIG. 21, the electrode body 200 is covered with the exterior members 101Z1 and 101Z2. The first sealing portion 110Z is formed by joining the opposing surfaces of the exterior members 101Z1 and 101Z2. In this example, each first sealing portion 110Z is folded toward the second surface 140Z side, not toward the first surface 130Z side. Even with this configuration, it is possible to achieve the effect of suppressing unevenness in the distribution of pressure applied to the lower electric storage device when multiple electric storage devices are stacked. When used in an all-solid-state battery, it is necessary to apply a high pressure uniformly from the outer surface of the battery to exhibit battery performance, so the packaging form of the present invention is preferable. In this example, each first sealing portion 110Z does not necessarily need to be folded. In this modification, each sealing portion 110Z may be sealed in a state in which it sandwiches a part of the electrode terminal 300. Furthermore, in this modification, each first sealing portion 110Z does not need to be formed on the side 135Z, and may protrude outward from approximately the center of the second surface 140Z in the thickness direction of the power storage device.
[0248] <5-2> In addition, in the above-mentioned embodiments 1-4, the electrode body 200 is a so-called stack type configured by stacking a plurality of electrodes 210, but the form of the electrode body 200 is not limited to this. The electrode body 200 may be, for example, a so-called wound type configured by winding a positive electrode and a negative electrode via a separator. The electrode body 200 may also be configured by stacking a plurality of so-called wound type electrode bodies.
[0249] <5-3> In the above-mentioned embodiment 1-4, the second surface 140 is a plane extending downward from the first surface 130 at a substantially right angle. However, the form of the second surface 140 is not limited to this. For example, consider a case where the electrode body 200 is a wound electrode body having a plane surface and a curved surface formed on the outer periphery. Here, it is assumed that the area of the plane surface is larger than the area of the curved surface, the first surface 130 covers the plane surface of the electrode body, and the second surface 140 covers the curved surface of the electrode body. In this case, the second surface 140 may be configured as a curved surface. In this case, the boundary portion where the second surface 140 extends downward from the first surface 130 is the side 135.
[0250] <5-4> In the third embodiment, bonding regions 151 are formed in four locations. However, the number of locations where bonding regions 151 are formed is not limited to this. For example, bonding regions 151 may be formed in two locations near both ends along side 135, in one location near the center of side 135, or in five or more locations.
[0251] <5-5> In the first embodiment, the electrode terminal 300 is disposed in the second sealing portion 120, but the position at which the electrode terminal 300 is disposed in the exterior body 100 is not limited thereto. For example, as shown in FIG. 22, the electrode terminal 300 can also be disposed in the first sealing portion 110. In other words, the first sealing portion 110 is sealed in a state in which the electrode terminal 300 is sandwiched between them. In this modification, at least one of the two electrode terminals 300 may be folded toward the second surface 140, may be folded toward the opposite side to the second surface 140, or may not be folded so as to protrude outward from the side 135. In this modification, the electrode terminal 300 and the first sealing portion 110 can be easily sealed, so that the sealing property of the exterior body 100 is improved. In addition, the electrode body 200 can be easily accommodated in the exterior body 100. In this modification, for example, the lid body 400 is fitted into each of the openings at both ends of the exterior member 101 as in the second embodiment. With the lid 400 fitted in place, the exterior member 101 and the lid 400 are heat sealed together to form the second sealed portion 120.
[0252] <5-6> In addition, in the above-mentioned second embodiment, the configuration of the lid body 400 can be arbitrarily changed. FIG. 23 is a perspective view showing a lid body 500 of a modified example of the lid body 400. The lid body 500 is, for example, plate-shaped, and includes a first surface 500A facing the electrode body 200 (see FIG. 9), and a surface 500B opposite to the first surface 500A. A hole 500C penetrating the first surface 500A and the second surface 500B is formed in the center of the lid body 500. The material constituting the lid body 500 is, for example, a resin. In this modified example, it is preferable that an adhesive film 530 that adheres to both the electrode terminal 300 and the lid body 500 is attached to a predetermined range including a portion of the electrode terminal 300 that is joined to the lid body 500. The lid 500 may be manufactured by being composed of a member divided into a first portion 510 and a second portion 520, and the first portion 510 and the second portion 520 are joined together so as to sandwich the electrode terminal 300 and the adhesive film 530. The lid 500 may also be manufactured by insert molding the lid 500 onto the electrode terminal 300 to which the adhesive film 530 is attached. In this modification, it is preferable that a barrier layer is laminated on at least a part of the surface of the lid 500. Alternatively, when the lid 500 has a plurality of layers, a barrier layer may be formed on any layer. The material constituting the barrier layer is, for example, aluminum. In this modification, when a gap occurs between the adhesive film 530 and the hole 530C, the gap is preferably filled with a resin material such as hot melt.
[0253] 24, in the exterior body 100X, the second sealing portion 120X is formed by joining the exterior member 101 and the second surface 500B of the lid body 500 with the lid body 500 fitted therein. The joining means between the exterior member 101 and the second surface 500B of the lid body 500 is, for example, heat sealing. In this modification, the exterior member 101 is joined to a wider area of the lid body 500, thereby improving the sealing performance of the exterior body 100X.
[0254] FIG. 25 is a front view of a lid body 600 of another modified example of the lid body 400 in the above-mentioned embodiment 2. The lid body 600 includes a metal part 610 that is a part where a metal is exposed on the surface, and the metal part 610 and the electrode 210 of the electrode body 200 are welded. The lid body 600 may be entirely composed of the metal part 610, or the metal part 610 may be partially formed. When the metal part 610 is partially formed, the lid body 600 is composed of a material having a multilayer structure including a metal layer. When the lid body 600 is composed of a material having a multilayer structure with a metal layer as an intermediate layer, the metal part 610 is a part where layers other than the metal layer are partially removed so that the metal layer is exposed. In the example shown in FIG. 25, the metal part 610 of the lid body 600 functions as an electrode terminal, so that a space between the lid body 600 and the electrode 210 is not required. Therefore, the electricity storage device 10X (see FIG. 9) can be configured to be small.
[0255] Fig. 26 is a front view of a lid body 700 which is another modified example of the lid body 400 in the above-mentioned embodiment 2. The lid body 700 includes a metal portion 710 made of a metal material, and a non-metal portion 720 connected to the metal portion 710 and made of a resin material. The metal portion 710 is welded to the electrode 210 of the electrode body 200. In the example shown in Fig. 26, the metal portion 710 of the lid body 700 functions as an electrode terminal, so that no space is required between the lid body 700 and the electrode 210. Therefore, the electricity storage device 10X (see Fig. 9) can be configured to be small in size.
[0256] <5-7> In the first embodiment, the second sealed portion 120 is formed by folding the exterior member 101 and heat-sealing the thermally adhesive resin layers of the exterior member 101. However, the method of forming the second sealed portion 120 is not limited to this. FIG. 27 is a plan view that shows a schematic diagram of an electricity storage device 10 having a second sealed portion 120Y of a modified example. The exterior member 101 has a protruding portion 101X that extends outward from the exterior body 100, and the thermally adhesive resin layers of the protruding portion 101X are heat-sealed to each other to form the second sealed portion 120Y. In the portion of the protruding portion 101X where the electrode terminal 300 is disposed, the thermally adhesive resin layer of the protruding portion 101X and the electrode terminal 300 are heat-sealed. According to this modified example, the second sealed portion 120Y can be heat-sealed more firmly, and therefore the hermeticity of the exterior body 100 is improved. In this modification, the protruding portion 101X may be cut as necessary except for the portion that is heat sealed to the electrode terminal 300. This modification can also be applied to the modification shown in FIG. [Explanation of symbols]
[0257] 10, 10X, 10XA, 10Y, 10Z Electric storage device, 100, 100X, 100Y Exterior body, 101, 101Y, 101Z1, 101Z2 Exterior member, 101A Base material layer, 101C Barrier layer, 101D Thermal adhesive resin layer, 101X Extension portion, 110, 110Z, 154 First sealing portion, 120, 120X, 120Y Second sealing portion, 130, 130Z First surface, 135, 135Z Side, 140, 140Z Second surface, 150 One portion, 151 Bonding region, 152 Space, 153 Unbonded region, 200 Electrode body, 210 Electrode, 215 Current collector, 300 Electrode terminal, 500A First surface, 500B 2nd side, 400,500,700 lid body, 610,710 metal part, C1 corner.
Claims
1. An exterior member for an electricity storage device, comprising: The power storage device is An electrode body; and an exterior body that seals the electrode body. The exterior body is formed of the film-like exterior member, The exterior body includes a first sealing portion, a first surface, and a second surface that are sealed by joining surfaces that face each other when the exterior member is wrapped around the electrode body, The area of the first surface is larger than the area of the second surface, The first sealing portion does not overlap the first surface in a plan view, the exterior member is composed of a laminate including at least a base layer, a barrier layer, and a heat-sealable resin layer in this order; The barrier layer includes an aluminum alloy foil having a composition of Fe: 0.2% by mass or more and 2.0% by mass or less, and Mg: 0.1% by mass or more and 5.0% by mass or less.
2. The exterior member according to claim 1 , wherein the aluminum alloy foil contains 0.10 mass % or less of Mn as an unavoidable impurity.
3. An exterior component as described in claim 1 or 2, wherein the aluminum alloy foil contains Cu: 0.10 mass% or less as an unavoidable impurity.
4. The exterior member according to claim 1 or 2, wherein the aluminum alloy foil has a composition satisfying Mg: more than 1.5 mass% and 5.0 mass% or less.
5. An exterior member as described in claim 1 or 2, wherein the remainder of the aluminum alloy foil other than Fe and Mg contains aluminum and unavoidable impurities, and the content of unavoidable impurities in the aluminum alloy foil which are components other than Fe, Mg, and Al is 0.10 mass% or less individually and 0.40 mass% or less in total.
6. The remainder further contains Si, The exterior member according to claim 5 , wherein the aluminum alloy foil has a composition satisfying a composition of Si: 0.5 mass % or less.
7. The exterior member according to claim 1 or 2, wherein the aluminum alloy foil has an orientation density of 15 or less in each of the Copper orientation and the R orientation of the texture.
8. The exterior member according to claim 1 or 2, wherein the aluminum alloy foil has an average crystal grain size of 25 μm or less.
